Method for using a porous membrane, separator for alkaline water electrolysis, and electrolyzer for alkaline water electrolysis

CN122996231APending Publication Date: 2026-10-27ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580021861.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-26
Filing Date
2025-03-25
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0065]根据本发明,能够提供一种碱性水电解用隔膜,该碱性水电解用隔膜即便使用片状的垫片,也能确保电解槽的气密性,同时能够以低槽电压进行碱性水电解。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996231A_ABST
    Figure CN122996231A_ABST
Patent Text Reader

Abstract

Disclosed is a diaphragm for alkaline water electrolysis, which is excellent in air tightness even when a sheet gasket is used and enables water electrolysis at a low cell voltage. The use method of the present invention is characterized in that a porous film containing polyethylene, the content of polyethylene in the resin component being 50% by mass or more and the tortuosity being 3.00 or less, is used as a diaphragm for alkaline water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method of using porous membranes, a diaphragm for alkaline water electrolysis, and an electrolyzer for alkaline water electrolysis. Background Technology

[0002] In recent years, hydrogen produced using renewable energy sources has garnered attention as a clean energy source for addressing issues such as global warming caused by CO2 and the depletion of fossil fuel reserves. Hydrogen production using renewable energy sources demands low costs comparable to existing fossil fuel-based reforming methods. Therefore, the production of hydrogen using renewable energy sources requires high levels of energy efficiency and low-cost equipment that are currently unattainable with existing technologies.

[0003] One industrial method for hydrogen production is water electrolysis. Compared to hydrogen production methods involving the reforming of fossil fuels, this method offers the advantage of obtaining high-purity hydrogen. In water electrolysis, an aqueous solution containing electrolytes such as sodium hydroxide or potassium hydroxide is typically used as the electrolyte to improve conductivity. Water is electrolyzed by applying a direct current to this electrolyte through the cathode and anode.

[0004] Alkaline water electrolysis is feasible on a large scale and is less expensive than other water electrolysis devices, thus it has proven successful as a commercially viable facility. Therefore, there is a desire to develop large-scale hydrogen production equipment using alkaline water electrolysis. For example, several concepts have been proposed, including the large-scale production of hydrogen through the electrolysis of alkaline water generated using natural energy sources such as wind or solar power, and the transportation and supply of hydrogen to consumption sites.

[0005] Electrolytic cells used for electrolysis (hereinafter sometimes referred to as "electrolysis") are divided into an anode chamber and a cathode chamber by a membrane. Oxygen is generated in the anode chamber, and hydrogen is generated in the cathode chamber. The membrane is required to have gas barrier properties so that the oxygen and hydrogen do not mix. In addition, in the electrolysis of water, the medium that transports electricity (electrons) is ions. For efficient electrolysis, the membrane is required to have high ion permeability. Considering this, membranes with porous structures (hereinafter sometimes referred to as "porous membranes") have been proposed as membranes that possess both gas barrier and ion permeability.

[0006] In addition, in order to perform electrolysis efficiently, it is desirable to reduce the solution resistance between the anode, cathode and diaphragm. Therefore, it is considered preferable to configure the diaphragm with two electrodes (sometimes referred to as "zero gap structure" below).

[0007] As a technology related to this diaphragm, patent documents 1 and 2 disclose a diaphragm for alkaline water electrolysis, which is a porous membrane formed by mixing zirconium oxide or magnesium oxide into polysulfone, which is an aromatic polymer resin, and using a non-solvent-induced phase separation method.

[0008] However, the aforementioned technologies still have room for improvement. For example, polyethersulfone and polysulfone, commonly used as membranes, contain ether groups in their repeating units, and therefore are gradually hydrolyzed in acidic or alkaline environments. During hydrolysis, the membrane structure changes, potentially leading to a decrease in membrane function and mechanical strength. This problem becomes more pronounced, especially under high temperature and high concentrations of acidic or alkaline conditions, where the hydrolysis rate increases.

[0009] On the other hand, ion permeability, expressed as conductivity, is closely related to the concentration and temperature of the electrolyte. For example, in high-temperature regions above 80°C, the conductivity of potassium hydroxide aqueous solution reaches its maximum at a concentration of approximately 30% by mass. Therefore, using a diaphragm under conditions of high conductivity to improve ion permeability may exacerbate the aforementioned hydrolysis rate problem.

[0010] Furthermore, polyethylene (hereinafter sometimes referred to as "PE"), a polyolefin resin, is widely used as a material with high chemical resistance, exhibiting very high resistance even in alkaline environments. Additionally, PE porous membranes, made from PE, are used in applications such as filters requiring mechanical strength and chemical resistance because they retain the properties of PE.

[0011] On the other hand, it is known that PE has high hydrophobicity and extremely poor wettability to electrolytes. Therefore, if it is used directly as a diaphragm, the electrolysis efficiency will be extremely poor. Patent documents 3, 4 and 5 disclose hydrophilic treatments such as introducing hydrophilic substances such as inorganic oxides into the porous structure and introducing hydrophilic resins and hydrophilic groups into the porous surface.

[0012] Existing technical documents

[0013] Patent documents

[0014] Patent Document 1: International Publication No. 93 / 15529

[0015] Patent Document 2: French Patent Application Publication No. 2546535

[0016] Patent Document 3: International Publication No. 2018-182006

[0017] Patent Document 4: International Publication No. 2014-119207

[0018] Patent Document 5: International Publication No. 2014-119208 Summary of the Invention

[0019] The problem that the invention aims to solve

[0020] However, in the prior art disclosed in the aforementioned patent documents 3, 4 and 5, the hydrophilic treatment of the porous surface of PE generates a large amount of blockage of the porous structure, thus reducing ion permeability. It is desirable to further improve the electrolysis performance.

[0021] Furthermore, in the prior art disclosed in Patent Documents 1 and 2, when the diaphragm is sandwiched between the anode and cathode, if the end of the diaphragm is exposed, airtightness cannot be ensured. Therefore, a gasket is needed to cover the entire area of ​​the outer periphery of the diaphragm. Thus, a gasket with a special structure for accommodating the outer periphery of the diaphragm is required, and it is desirable to ensure airtightness by using a sheet-like gasket with better lamination operability.

[0022] The present invention was made in view of the above circumstances, and its object is to realize a diaphragm that has good airtightness even when using sheet gaskets and can perform water electrolysis at low cell voltage.

[0023] Methods for solving problems

[0024] Therefore, the inventors conducted repeated and in-depth research to solve the above-mentioned problems. As a result, they found that by using a porous membrane with a polyethylene content and tortuosity within a specific range, the porous structure of the part fastened by the gasket will be blocked to ensure airtightness. On the other hand, the part held by the anode and cathode maintains the above-mentioned tortuosity within a specific range of void structure, maintaining high ion permeability. Thus, water electrolysis can be performed with a low cell voltage, thereby completing the present invention.

[0025] That is, the present invention is as follows. [1]

[0027] A method of use, characterized in that a porous membrane containing polyethylene, resin components, and a polyethylene content of 50% or more and a tortuosity of 3.00 or less is used as a diaphragm for alkaline water electrolysis. [2]

[0029] According to the method of use described in [1], the thickness of the porous membrane is more than 40 μm and less than 1000 μm. [3]

[0031] According to the method of use described in [1] or [2], the tortuosity of the porous membrane is 0.30 or more and 2.50 or less. [4]

[0033] According to the method of use described in [1] or [2], the tortuosity of the porous membrane is 1.00 or more and 2.50 or less. [5]

[0035] According to any one of [1] to [4], the porosity of the porous membrane is 20% or more and 95% or less. [6]

[0037] According to any one of [1] to [5], the water permeability of the porous membrane is more than 0.1 g / 2 min and less than 500 g / 2 min. [7]

[0039] According to any one of [1] to [6], the air permeability of the porous membrane is 10 seconds to 4000 seconds when converted to 100 μm. [8]

[0041] According to any one of [1] to [7], the viscosity-average molecular weight of the polyethylene is more than 300,000 and less than 7,500,000. [9]

[0043] A diaphragm for alkaline water electrolysis is characterized in that it comprises a porous membrane containing polyethylene, wherein the content of polyethylene in the resin component of the porous membrane is 50% by mass or more, and the tortuosity of the porous membrane is 3.00 or less.

[10]

[0045] According to the alkaline water electrolysis diaphragm described in [9], the membrane thickness is more than 40 μm and less than 1000 μm.

[11]

[0047] According to the alkaline water electrolysis diaphragm described in [9] or

[10] , the tortuosity of the porous membrane is 0.30 or more and 2.50 or less.

[12]

[0049] According to the alkaline water electrolysis diaphragm described in [9] or

[10] , the tortuosity of the porous membrane is 1.00 or more and 2.50 or less.

[13]

[0051] The alkaline water electrolysis diaphragm according to any one of [9] to

[12] , wherein the porosity of the porous membrane is 20% or more and 95% or less.

[14]

[0053] The alkaline water electrolysis diaphragm according to any one of [9] to

[13] , wherein the water permeability of the porous membrane is more than 0.1 g / 2 min and less than 500 g / 2 min.

[15]

[0055] The alkaline water electrolysis diaphragm according to any one of [9] to

[14] , wherein the air permeability of the porous membrane is 10 seconds to 4000 seconds when converted to 100 μm.

[16]

[0057] The diaphragm for alkaline water electrolysis according to any one of [9] to

[15] , wherein the viscosity-average molecular weight of the polyethylene is more than 300,000 and less than 7,500,000.

[17]

[0059] An electrolytic cell for alkaline water electrolysis, comprising: The diaphragm for alkaline water electrolysis as described in any one of [9] to

[16] ; Anode; and cathode, The aforementioned diaphragm for alkaline water electrolysis is disposed between the aforementioned anode and the aforementioned cathode.

[18]

[0061] An electrolytic cell for alkaline water electrolysis, comprising: The diaphragm for alkaline water electrolysis as described in any one of [9] to

[16] ; Sheet gaskets; Anode; and cathode, The aforementioned diaphragm for alkaline water electrolysis is disposed between the aforementioned anode and the aforementioned cathode.

[19]

[0063] An electrolytic cell for alkaline water electrolysis, comprising: The diaphragm for alkaline water electrolysis as described in any one of [9] to

[16] ; Two sheet-like gaskets; Anode; and cathode, The aforementioned diaphragm for alkaline water electrolysis is disposed between the aforementioned anode and the aforementioned cathode, and the aforementioned two sheet-like gaskets are arranged in such a way as to clamp the aforementioned diaphragm for alkaline water electrolysis.

[0064] The effects of the invention

[0065] According to the present invention, a diaphragm for alkaline water electrolysis can be provided, which can ensure the airtightness of the electrolytic cell even when using sheet-like gaskets, and can perform alkaline water electrolysis at a low cell voltage. Attached Figure Description

[0066] Figure 1 This is a side view showing an example of a bipolar electrolyzer for alkaline water electrolysis according to this embodiment.

[0067] Figure 2 This is a side view of the portion of the dashed box showing an example of the zero-gap structure of the bipolar electrolyzer for alkaline water electrolysis according to this embodiment.

[0068] Figure 3This is a top view showing an example of the electrode chamber portion of the bipolar electrolyzer for alkaline water electrolysis according to this embodiment.

[0069] Figure 4 This is a schematic diagram of an alkaline water electrolysis apparatus having an example of a bipolar electrolyzer for alkaline water electrolysis according to this embodiment. Detailed Implementation

[0070] The embodiments of the present invention (hereinafter referred to as "this embodiment") will be described in detail below. It should be noted that the present invention is not limited to the following embodiments, and various modifications can be made within its scope.

[0071] <Diaphragm for alkaline water electrolysis>

[0072] The alkaline water electrolysis diaphragm of this embodiment is characterized by having a porous membrane of this embodiment containing 50% by mass or more polyethylene in the resin composition and having a tortuosity of 3.00 or less.

[0073] The diaphragm for alkaline water electrolysis in this embodiment at least includes the porous membrane of this embodiment, and may further include other components such as a support. Preferably, the diaphragm for alkaline water electrolysis in this embodiment is composed only of the porous membrane of this embodiment.

[0074] It should be noted that in this instruction manual, the diaphragm used for alkaline water electrolysis is sometimes simply referred to as "diaphragm".

[0075] In an electrolytic cell, a diaphragm is positioned between the anode and the cathode to allow the electrolyte containing ions to pass through while blocking the gas generated at the two electrodes.

[0076] The porous membrane in this embodiment is preferably a porous membrane assembled before being attached to the alkaline water electrolysis membrane. For example, the porous membrane described above may not have conductive components (e.g., anode, cathode, etc.) disposed on either surface.

[0077] The diaphragm for alkaline water electrolysis in this embodiment is preferably an alkaline water electrolysis diaphragm disposed before being placed in the electrolytic cell. For example, the above-mentioned alkaline water electrolysis diaphragm may not have conductive components (such as the anode and cathode of the electrolytic cell) disposed on either of its surfaces.

[0078] The porous membrane of the alkaline water electrolysis diaphragm in this embodiment is preferably formed of a resin composition containing polyethylene. In addition to polyethylene, the resin composition may further contain other components such as additives described later. Preferably, the resin composition contains only polyethylene as the resin component, but it may also be a resin composition consisting solely of polyethylene.

[0079] Polyethylene has a main chain backbone that is not easily hydrolyzed, making it difficult to dissolve and decompose in an alkaline environment. However, if substances that impart hydrophilicity are added to alkali-resistant resins like polyethylene, it is preferable that the porous membrane be composed solely of alkali-resistant resins, considering the potential for reduced strength and deterioration of permeability. Specific examples of alkali-resistant resins other than polyethylene include polyphenylene sulfide (PPS) resin and polyether ether ketone (PEEK) resin.

[0080] Examples of polyethylene include low-density PE (density 0.910 g / cm³). 3 Above and less than 0.930 g / cm 3 ), linear low-density PE (density 0.910 g / cm³) 3 Above and below 0.940 g / cm³ 3 Medium density PE (density 0.930 g / cm³) 3 Above and below 0.942 g / cm³ 3 High-density PE (density 0.942 g / cm³) 3 (Above) etc. They can be used alone or in combination of two or more. Among them, from the perspective of obtaining a porous membrane with uniform physical properties, it is preferred to use PE alone.

[0081] From the perspective of improving the resistance to decomposition under high temperature conditions in concentrated alkaline aqueous solutions, the content of PE in the resin component contained in the porous membrane is 50% by mass or more, preferably 65% ​​by mass or more, more preferably 70% by mass or more, further preferably 75% by mass or more, further preferably 80% by mass or more, further preferably 85% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, particularly preferably 99% by mass or more, and may also be 100% by mass (which may consist of PE alone).

[0082] It should be noted that the content of resin component in the porous membrane is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and may also be 100% by mass (which may consist of only resin component).

[0083] Furthermore, from the perspective of improving the resistance to decomposition under high temperature conditions in concentrated alkaline aqueous solutions, the PE content in the porous membrane is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and may also be 100% by mass (which may consist of only PE).

[0084] Here, the proportion of resin contained in the porous membrane can be determined, for example, by weight change based on thermogravimetric analysis (TGA) or by a combination of thermal decomposition GC-MS and TGA.

[0085] From the perspective of balancing ion permeability and membrane mechanical strength, high-density PE with a viscosity-average molecular weight of 300,000 or more is preferred, high-density PE with a viscosity-average molecular weight of 900,000 or more is even more preferred, and ultra-high molecular weight PE with a viscosity-average molecular weight of 2 million or more is even more preferred. On the other hand, from the perspective of film-forming properties, PE with a viscosity-average molecular weight of 10 million or less is preferred, more preferably PE with a viscosity-average molecular weight of 7.5 million or less is even more preferred, and PE with a viscosity-average molecular weight of 4 million or less is even more preferred. From the perspective of maintaining high melt tension during melt molding to ensure good formability, or imparting sufficient winding to the resin to improve the mechanical strength of the porous membrane, a viscosity-average molecular weight of 300,000 or more is preferred for the PE. On the other hand, from the perspective of achieving uniform melt mixing and improving sheet formability, especially thickness formability, a viscosity-average molecular weight of 10 million or less is preferred for the PE. Furthermore, from the perspective of further improving thickness formability, a viscosity-average molecular weight of 7.5 million or less is preferred.

[0086] It should be noted that the viscosity-average molecular weight Mv of PE can be calculated based on the intrinsic viscosity [η] (dl / g) of decahydronaphthalene solvent at 135°C using ASTM-D4020, and then obtained by the following formula.

[0087] [η] = 6.77 × 10 -4 Mv 0.67

[0088] It should be noted that, in the resin composition containing PE used to manufacture the above-mentioned porous membrane, various known additives may be mixed as needed, such as phenolic, phosphorus-based, and sulfur-based antioxidants; metal soaps such as calcium stearate and zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; coloring pigments; etc.

[0089] For the porous membrane of the alkaline water electrolysis diaphragm of this embodiment, from the perspective of good ion permeability and the ability to achieve low electrolysis voltage, the tortuosity is 3.00 or less, preferably 2.70 or less, more preferably 2.50 or less, further preferably 2.40 or less, further preferably 2.20 or less, and even more preferably 2.00 or less. There is no particular lower limit for the tortuosity; for example, from the perspective of achieving good puncture strength per 100 μm thickness of the porous membrane, it is preferably greater than 0, more preferably 0.30 or more, further preferably 0.50 or more, further preferably 0.60 or more, and even more preferably 1.00 or more.

[0090] In alkaline water electrolysis, as is common knowledge to those skilled in the art, the situation differs greatly from that using non-aqueous electrolytes. It is difficult for the electrolyte to enter the pores of the porous membrane containing PE (PE porous membrane), making it difficult to achieve a low cell voltage. In researching this invention, it was discovered, for example, that by pre-immersing the PE porous membrane in a hydrophilic solvent (e.g., ethanol) and then immersing it in a solvent (e.g., water (distilled water)), the hydrophilic solvent and the solvent (e.g., water) within the pores can be replaced, filling the pores with the solvent (e.g., water). However, if the pores are pre-filled with the solvent (e.g., water), then during electrolysis using a PE membrane equipped with this PE porous membrane, even if ion movement occurs due to the electrolysis reaction, the electrolyte will flow into the pores and be retained, thus enabling continuous electrolysis.

[0091] However, it is known that if the tortuosity of the PE porous membrane exceeds 3.00, the initial cell voltage rises sharply when electrolyzing using a PE diaphragm equipped with this PE porous membrane, which cannot be explained simply by increasing the distance of the ion conduction path. Although the mechanism is not yet certain, it is believed that in the case of PE porous membranes, if the tortuosity exceeds 3.00, even when using hydrophilic solvents such as ethanol, a portion of the pores (voids) of the PE porous membrane will not be filled by the solvent or hydrophilic solvent, thus leaving unfilled areas of electrolyte, resulting in a sharp rise in cell voltage.

[0092] Furthermore, PE porous membranes, being porous materials of PE, are easily deformed when pressure is applied in a direction perpendicular to the membrane surface (the thickness direction). This is because the fibrous portions of the PE porous membrane undergo plastic deformation at room temperature, thereby clogging the pores (voids).

[0093] Based on these findings, the inventors discovered that in areas where the sheet gasket is used for fastening (applying pressure), the pores are blocked, resulting in good airtightness. On the other hand, in areas where the anode and cathode are clamped (not subjected to pressure by the sheet gasket), the tortuosity is maintained. Therefore, if the tortuosity of the PE porous membrane is 3.00 or less, a low tank voltage can be achieved. In other words, by using a diaphragm with a PE porous membrane having a tortuosity of 3.00 or less, both airtightness (sealing) and low tank voltage can be achieved even when using sheet gaskets.

[0094] It should be noted that the tortuosity can be adjusted by adjusting the viscosity-average molecular weight of PE, the proportion of PE in the resin composition in the mixing process described later (a), the stretching temperature and stretching ratio in the primary stretching process of the manufacturing method of the porous membrane containing polyethylene described later (d), and / or by adjusting the temperature and stretching ratio of the heat setting process (stretching and relaxation operation) described later (f).

[0095] Regarding the porous membrane of this embodiment, the final membrane thickness is preferably 40 μm or more, more preferably 50 μm or more, further preferably 70 μm or more, preferably 1000 μm or less, more preferably 650 μm or less, further preferably 300 μm or less, and most preferably 250 μm or less.

[0096] Regarding the diaphragm for alkaline water electrolysis in this embodiment, its final membrane thickness is preferably 40 μm or more, more preferably 50 μm or more, even more preferably 70 μm or more, preferably 1000 μm or less, more preferably 650 μm or less, even more preferably 300 μm or less, and most preferably 250 μm or less.

[0097] From the perspectives of preventing initial short circuits in the diaphragm and improving mechanical strength, a diaphragm thickness of 40 μm or more is preferred. On the other hand, a diaphragm thickness of 1000 μm or less is preferable as it allows for closer proximity between electrodes and tends to reduce cell voltage during electrolysis.

[0098] The porosity of the porous membrane in this embodiment is preferably 20% or more, more preferably 30% or more, further preferably 45% or more, preferably 95% or less, more preferably 80% or less, and further preferably 70% or less. From the perspective of reducing cell voltage when using the porous membrane in alkaline water electrolysis, a porosity of 20% or more is preferred. On the other hand, from the perspective of ensuring high puncture strength, a porosity of 95% or less is preferred. Furthermore, from the perspective of avoiding membrane damage due to excessive stretching during stretching and / or heat setting processes, which would reduce ion permeability, this is also preferred.

[0099] It should be noted that the porosity mentioned above can be adjusted by adjusting the stretching temperature, stretching ratio, and stretching strain rate in the first stretching process described later (d), and / or by adjusting the temperature and stretching ratio in the heat setting process (stretching and relaxation operation) described later (f).

[0100] From the perspective of good ion permeability and reduced cell voltage, the water permeability of the porous membrane in this embodiment is preferably 0.1g / 2min or more, more preferably 0.5g / 2min or more, and even more preferably 1.0g / 2min or more. From the perspective of good puncture strength, it is preferably 500g / 2min or less, more preferably 100g / 2min or less, and even more preferably 10g / 2min or less.

[0101] It should be noted that the above-mentioned water permeability can be adjusted by adjusting the stretching temperature, stretching ratio, and stretching strain rate in the stretching process described later (d), and / or by adjusting the temperature and stretching ratio in the heat setting process (stretching and relaxation operation) described later (f).

[0102] From the perspective of maintaining the mechanical strength and gas barrier properties of the porous membrane, the air permeability of the porous membrane in this embodiment, calculated based on a thickness of 100 μm, is preferably 10 seconds or more, more preferably 20 seconds or more, further preferably 50 seconds or more, and particularly preferably 100 seconds or more. On the other hand, from the perspective of reducing the cell voltage during electrolysis, it is preferably 4000 seconds or less, more preferably 3000 seconds or less, and further preferably 2500 seconds or less.

[0103] It should be noted that the above-mentioned air permeability can be adjusted by adjusting the temperature and expansion ratio of the heat setting process (stretching and relaxation operation) described later (f).

[0104] From the perspective of suppressing membrane damage during the assembly of the electrolysis unit and suppressing short circuits caused by contact between the electrode and the diaphragm due to vibrations generated during electrolysis, the puncture strength of the porous membrane in this embodiment, measured in terms of puncture strength per 100 μm membrane thickness, is preferably 90 gf / 100 μm or more, more preferably 200 gf / 100 μm or more, and even more preferably 500 gf / 100 μm or more. On the other hand, from the perspective of reducing diaphragm width shrinkage during electrolysis, it is preferably 10000 gf / 100 μm or less, more preferably 8000 gf / 100 μm or less, and even more preferably 6000 gf / 100 μm or less.

[0105] It should be noted that the above-mentioned puncture strength can be adjusted by adjusting the molecular weight of PE, the proportion of PE in the resin composition in the mixing process described later (a), the stretching temperature and stretching ratio in the primary stretching process described later (d), and / or by adjusting the temperature and stretching ratio of the heat setting process (stretching and relaxation operation) described later (f).

[0106] (Gas Barrier Performance Evaluation)

[0107] One of the evaluation indicators for the gas barrier properties of the porous membrane in this embodiment is the bubble point evaluation. In this evaluation method, the bubble point is determined by fully wetting the porous membrane with pure water, filling the pores with pure water, pressurizing one side of the porous membrane with nitrogen gas, and continuously generating bubbles from the opposite side of the porous membrane at a rate of 150 mL / min. The lower the gas barrier properties of the porous membrane, the smaller the bubble point value; conversely, the higher the gas barrier properties of the porous membrane, the more difficult it is for gas to pass through, and therefore the larger the bubble point value.

[0108] The bubble point of the porous membrane in this embodiment is preferably 0.1 MPa or higher. If the bubble point of the porous membrane is 0.1 MPa or higher, the separation capability of the porous membrane can be ensured. Furthermore, when the porous membrane is used as a separator in electrolysis, even when there is a pressure difference between the cathode and anode chambers, the generated gas cannot easily permeate through the separator, thus effectively suppressing the mixing of oxygen and hydrogen. From this perspective, the bubble point of the porous membrane is more preferably 0.2 MPa or higher, further preferably 0.4 MPa or higher, and most preferably 0.6 MPa or higher.

[0109] It should be noted that the bubble point can be determined using the following method. Wet the porous membrane sample with pure water, allowing the water to permeate into the pores of the membrane, and place it in a pressure-resistant container for testing. Next, maintain the pressure-resistant container in a thermostatic bath set to a specified temperature. After the specified temperature is reached inside the pressure-resistant container, begin the test using an integrity testing machine (e.g., Sartorius Stedim Japan, "Sartocheck Junior BP-Plus"). After the test begins, pressurize the upper surface of the sample with nitrogen. The pressure of the nitrogen gas at which bubbles are continuously generated from the lower surface of the sample at a rate of 150 mL / min is taken as the bubble point pressure (MPa).

[0110] Even without special hydrophilization treatment, the diaphragm for alkaline water electrolysis in this embodiment will hardly damage the original porous structure as long as the pores of the porous membrane are filled with a certain volume fraction of solvent in advance, and water electrolysis can be carried out continuously for a long time with low cell voltage.

[0111] There are no particular limitations. For example, if more than 40% of the pores of the porous membrane are pre-filled with a solvent such as water, the continuous layer of electrolyte within the pores will not be interrupted even if ions and electrolyte move due to the water electrolysis reaction, allowing for more continuous water electrolysis, which is therefore preferable. In particular, in the case of porous membranes with a porous structure having high ion permeability, it is considered that water electrolysis can be performed at low cell voltages.

[0112] From the perspective of high ion permeability, it is more preferable to prefill at least 54% of the pores of the porous membrane with a solvent (e.g., water), even more preferably to prefill at least 68% with a solvent (e.g., water), and even more preferably to prefill at least 88% with a solvent (e.g., water).

[0113] The method for filling the pores of a porous membrane with a solvent (e.g., water) is not particularly limited, but the following method is preferred: immersing the porous membrane in a hydrophilic solvent, filling the pores with the hydrophilic solvent, and then immersing the porous membrane in a solvent (e.g., water), thereby displacing the hydrophilic solvent and the solvent (e.g., water) within the pores, and finally filling the pores with the solvent (e.g., water). In the case of a hydrophilic solvent with high surface tension, it is difficult to fully fill the pores of the porous membrane with this solvent; therefore, a hydrophilic solvent with a surface tension of 34 mN / m or less is more preferred. In particular, this is more preferred for porous membranes with a contact angle with water greater than 70°.

[0114] It should be noted that the contact angle between a porous membrane and water refers to the angle formed when a water droplet is dropped onto the surface of a porous membrane that has been hot-pressed into a flat plate shape, and a tangent line is drawn from the point of contact between the water droplet and the plate surface. The contact angle between the plate and water can be measured using a commercially available contact angle meter via the θ / 2 method.

[0115] Examples of hydrophilic solvents include methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, and acetonitrile. Alternatively, it is preferable to use an aqueous solution mixed with water without using the hydrophilic solvent alone. In this case, it is also preferable to use an aqueous solution with a surface tension of 34 mN / m or less, such as a 30% by mass aqueous solution of ethanol (surface tension 33 mN / m) or a 50% by mass aqueous solution of ethanol (surface tension 28 mN / m).

[0116] The aforementioned hydrophilic solvent preferably comprises one or more selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, acetone, and acetonitrile. Furthermore, the aforementioned hydrophilic solvent is preferably an aqueous solution comprising 30% by mass or more of one or more selected from the group consisting of methanol, ethanol, 1-propanol, 2-propanol, acetone, and acetonitrile.

[0117] Furthermore, the hydrophilic solvent is not particularly limited, but is more preferably an organic solvent with a solubility of 50 g / L or more in water at 20°C. From the perspective that the displacement to water is faster when the solvent inside the pores of the porous membrane is water, the solubility of this organic solvent in water is more preferably 100 g / L or more, and even more preferably 200 g / L or more.

[0118] The proportion of solvent (e.g., water) filling the pores of the porous membrane can be adjusted by appropriately adjusting the time for immersing the porous membrane in the hydrophilic solvent and the time for immersing the porous membrane in the solvent (e.g., water). Depending on the circumstances, the proportion of solvent filling the pores can also be adjusted by incorporating a process for drying the porous membrane after immersing it in the solvent (e.g., water).

[0119] Examples of solvents that can fill the pores of a porous membrane include: water; the aforementioned hydrophilic solvents (preferably hydrophilic solvents with a surface tension of 34 mN / m or less); alkaline aqueous solutions such as NaOH aqueous solution and KOH aqueous solution (e.g., alkaline aqueous solutions with an alkali metal salt concentration of more than 0% by mass and less than 40% by mass (preferably more than 0% by mass and less than 35% by mass)); and combinations thereof; etc. Among these, hydrophilic solvents (more preferably hydrophilic solvents with a surface tension of 34 mN / m or less) and water are preferred from the perspective of easier displacement to the electrolyte during alkaline water electrolysis and a further extended period for continuous electrolysis.

[0120] It should be noted that, unless otherwise specified, all the above parameters shall be measured according to the measurement methods described in the embodiments below.

[0121] The porous membrane of this embodiment may contain inorganic compounds. There are no particular limitations on the content of inorganic compounds in the porous membrane, as long as it does not clog the porous structure and impair ion permeability. For example, it may be 10% by mass or more, 20% by mass or more, 30% by mass or more, or 90% by mass or less, 80% by mass or less, or 70% by mass or less.

[0122] Here, the inorganic compounds preferably do not dissolve or decompose in an alkaline environment. Furthermore, the inorganic compounds can adhere to the surface of the porous membrane, or they can be partially or completely embedded in the resin constituting the porous membrane.

[0123] Examples of inorganic compounds include, for instance, oxides or hydroxides of zirconium, titanium, bismuth, and cerium; oxides of Group IV elements of the periodic table; hydroxides of Group IV elements of the periodic table; nitrides of Group IV elements of the periodic table; and carbides of Group IV elements of the periodic table. From the perspective of chemical stability, oxides of zirconium, titanium, bismuth, and cerium, and oxides or hydroxides of Group IV elements of the periodic table are preferred, with zirconium oxide (ZrO2), zirconium hydroxide (Zr(OH)4), titanium oxide (TiO2), and titanium hydroxide (Ti(OH)4) being more preferred. They can be used individually or in combination of two or more. As the electrolyte for alkaline water electrolysis, alkaline aqueous solutions such as NaOH and KOH are frequently used. If titanium oxide is exposed to such an environment, it sometimes transforms into titanates such as sodium titanate or potassium titanate. Therefore, titanates can also be used beforehand.

[0124] The size of the inorganic compound is not particularly limited, but in the case of particulate matter, the average primary particle size is preferably 10 nm to 300 nm, more preferably 25 nm to 250 nm.

[0125] The average primary particle size of particulate inorganic compounds (sometimes referred to as "inorganic particles" below) in a porous membrane can be determined using the following method. The sample is observed perpendicular to the surface of the porous membrane using a scanning electron microscope (SEM) at a magnification sufficient to visualize the particulate inorganic compounds. The image is then binarized using image analysis software (ImageJ), and the absolute maximum length of 10 unaggregated particulate inorganic compounds is measured, with the average number of these lengths calculated. It should be noted that when the particulate inorganic compounds are not present on the surface of the porous membrane but only within it, the cut cross-section can be observed using SEM.

[0126] The porous membrane of this embodiment comprises polyethylene. Preferably, the polyethylene content in the resin component is 50% by mass or more (it can be 65% by mass or more, 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass), the tortuosity is 3.00 or less (it can be 2.70 or less, 2.50 or less, 2.40 or less, 2.20 or less, 2.00 or less, or more than 0, 0.30 or more, 0.50 or more, 0.60 or more, 1.00 or more), and the membrane thickness is 40 μm or more and 1000 μm or less (it can be 50 μm or more, 70 μm or more, or more than 650 μm, 300 μm or less, 25 μm or less). The polyethylene has the following properties: pore size (below 0 μm), porosity (above 20% and below 95%, which can be above 30% or 45%, or below 80% or 70%), water permeability (above 0.1 g / 2 minutes and below 500 g / 2 minutes), air permeability (converted to 100 μm) (above 10 seconds and below 4000 seconds), air permeability (converted to 100 μm) (above 20 seconds, above 50 seconds, or above 100 seconds, or below 3000 seconds or below 2500 seconds), and viscosity-average molecular weight (below 300,000 and below 10,000,000), which can be above 900,000 or above 2,000,000, or below 7,500,000 or below 4,000,000.

[0127] The diaphragm for alkaline water electrolysis in this embodiment can be a single-layer structure consisting only of a porous membrane, or it can be a laminated structure containing other layers in addition to a porous membrane.

[0128] For the alkaline water electrolysis membrane of this embodiment, from the perspective of suppressing swelling caused by electrolyte, preventing clogging of porous structures, and ensuring good ion permeability, it is preferable that the surface inside the alkaline water electrolysis membrane (the surface of the pores) is not modified with functional groups that have anion exchange capacity, specifically monomers such as amino, amide, cyano, and imidazole groups.

[0129] It should be noted that the presence or absence of the above-mentioned surface modifications can be evaluated, for example, by FT-IR measurement of the cross-section of the fibrous portion at the center of the diaphragm surface and the diaphragm cross-section.

[0130] The alkaline water electrolysis diaphragm of this embodiment may have a support. This support only needs to be ion-permeable and may be porous or non-porous. Among these, a porous support is preferred from the perspective of not substantially reducing ion permeability. The porous support mainly serves as the core material in the alkaline water electrolysis diaphragm, improving the mechanical strength of the diaphragm. The porous support preferably does not substantially reduce ion permeability. The material of the porous support is not particularly limited; examples include polyphenylene sulfide, polyethylene, polypropylene, fluorinated resins, poly(p-phenylenebenzodioxazole), polyketone, polyimide, and polyetherimide. These can be used individually or in combination with two or more materials.

[0131] The shape of the porous support can be, for example, sheet-like. Examples of porous supports include membrane-like porous materials, nonwoven fabrics, woven fabrics, or composite fabrics comprising nonwoven fabrics and woven fabrics contained within the nonwoven fabrics. These can be used individually or in combination. On the other hand, from the perspective of ion permeability, the diaphragm for alkaline water electrolysis in this embodiment preferably does not have a porous support, and more preferably, it does not have a support at all. Without a support, the volume of the support increases in areas related to ion permeability, thus sometimes enabling water electrolysis with high ion permeability and low cell voltage.

[0132] The diaphragm for alkaline water electrolysis in this embodiment comprises a porous membrane containing polyethylene. Preferably, the polyethylene content in the resin component of the porous membrane is 50% by mass or more (it can be 65% by mass or more, 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass), the tortuosity of the porous membrane is 3.00 or less (it can be 2.70 or less, 2.50 or less, 2.40 or less, 2.20 or less, 2.00 or less, or more than 0, 0.30 or more, 0.50 or more, 0.60 or more, or 1.00 or more), and the membrane thickness of the diaphragm for alkaline water electrolysis is 40 μm or more and 1000 μm or less (it can be 50 μm or more, 70 μm or more, or more than 650 μm, 300 μm or less). The porous membrane has a porosity of 20% to 95% (can be 30% or more, 45% or more, or 80% or less, or 70%), a water permeability of 0.1g / 2min to 500g / 2min (can be 0.5g / 2min to 1.0g / 2min or more, or 100g / 2min or less, or 10g / 2min or less), an air permeability of 10 seconds to 4000 seconds (can be 20 seconds to 50 seconds to 100 seconds, or 3000 seconds or less, or 2500 seconds or less) and a viscosity-average molecular weight of polyethylene contained in the porous membrane of 300,000 to 10,000,000 (can be 900,000 to 2,000,000, or 7,500,000 or less, or 4,000,000 or less).

[0133] <How to Use Porous Membranes>

[0134] The method of using the porous membrane in this embodiment is characterized by using a porous membrane containing 50% by mass or more polyethylene in the resin composition and having a tortuosity of 3.00 or less as a diaphragm for alkaline water electrolysis.

[0135] The porous membrane used in the above-described method is preferably the porous membrane described in this embodiment.

[0136] In addition, the aforementioned diaphragm for alkaline water electrolysis preferably does not include a support.

[0137] The porous membrane comprises polyethylene. Preferably, the polyethylene content in the resin component is 50% by mass or more (which can be 65% by mass or more, 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass), the tortuosity is 3.00 or less (which can be 2.70 or less, 2.50 or less, 2.40 or less, 2.20 or less, 2.00 or less, or more than 0, 0.30 or more, 0.50 or more, 0.60 or more, 1.00 or more), and the membrane thickness is 40 μm or more and 1000 μm or less (which can be 50 μm or more, 70 μm or more, or more than 650 μm, 300 μm or less, 250 μm or less). The following properties are required: porosity of 20% to 95% (can be 30% or more, 45% or more, or 80% or less, or 70% or less); water permeability of 0.1g / 2 minutes to 500g / 2 minutes (can be 0.5g / 2 minutes to 1.0g / 2 minutes to 100g / 2 minutes to 10g / 2 minutes to 10 minutes to ...

[0138] <Instructions for using diaphragms in alkaline water electrolysis>

[0139] The method of using the alkaline water electrolysis diaphragm of this embodiment is characterized by using an alkaline water electrolysis diaphragm having a porous membrane containing polyethylene, wherein the content of polyethylene in the resin component of the porous membrane is 50% by mass or more, and the tortuosity of the porous membrane is 3.00 or less.

[0140] The porous membrane used in the alkaline water electrolysis diaphragm of the above-described method is preferably the porous membrane described in this embodiment.

[0141] In addition, the aforementioned diaphragm for alkaline water electrolysis preferably does not include a support.

[0142] The diaphragm for alkaline water electrolysis comprises a porous membrane containing polyethylene. Preferably, the polyethylene content in the resin component of the porous membrane is 50% by mass or more (which can be 65% by mass or more, 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass), the tortuosity of the porous membrane is 3.00 or less (which can be 2.70 or less, 2.50 or less, 2.40 or less, 2.20 or less, 2.00 or less, or more than 0, 0.30 or more, 0.50 or more, 0.60 or more, 1.00 or more), and the membrane thickness of the diaphragm for alkaline water electrolysis is 40 μm or more and 1000 μm or less (which can be 50 μm or more, 70 μm or more, or more than 650 μm, 300 μm or less, or more than 1000 μm). The porous membrane has a porosity of 20% to 95% (can be 30% or more, 45% or more, or 80% or less, or 70% or less), a water permeability of 0.1g / 2min to 500g / 2min (can be 0.5g / 2min to 1.0g / 2min or more, or 100g / 2min or less, or 10g / 2min or less), an air permeability of 100μm to 4000 seconds (can be 20 seconds or more, 50 seconds or more, or 100 seconds or more, or 3000 seconds or less, or 2500 seconds or less), and a viscosity-average molecular weight of polyethylene contained in the porous membrane is 300,000 to 10,000,000 (can be 900,000 to 2,000,000, or 7,500,000 or less, or 4,000,000 or less).

[0143] <Manufacturing Method of Diaphragm for Alkaline Water Electrolysis>

[0144] The diaphragm for alkaline water electrolysis in this embodiment is not particularly limited, and can be manufactured by known methods, preferably including the following steps. These steps are not limited in number and can be selected appropriately.

[0145] [Method for manufacturing a porous membrane containing polyethylene]

[0146] The method for manufacturing the porous membrane containing polyethylene (hereinafter sometimes referred to as "polyethylene porous membrane") in this embodiment is not particularly limited, and can be manufactured by known dry film forming method, melt film forming method, wet film forming method, etc.

[0147] For example, a method can be described including the following steps: a mixing step (a), mixing a resin composition containing polyethylene and a pore-forming material; an extrusion step (b), melting and extruding the mixture obtained in step (a); a sheet forming step (c), forming the extrudate obtained in step (b) into a sheet; a primary stretching step (d), stretching the sheet obtained in step (c) at least once in a uniaxial direction; an extraction step (e), extracting the pore-forming material from the stretched film obtained in step (d); and a heat-setting step (f), heat-setting the extracted film obtained in step (e) at a specified temperature. Alternatively, the above method can be used to further perform a secondary stretching step (g) after the extraction step (e) followed by the heat-setting step (f). Alternatively, the extraction step (e) can be performed immediately after the sheet forming step (c), followed by the primary stretching step (d) and the heat-setting step (f).

[0148] The above-described method for manufacturing porous polyethylene membranes provides a high-performance porous polyethylene membrane suitable for use as a diaphragm in alkaline water electrolysis cells and other electrochemical devices, particularly in applications requiring high-temperature, high-concentration alkaline environments. The method involving stretching on MD and TD in the initial stretching step (d), followed by extraction step (e) and heat setting on TD in the heat setting step (f), tends to readily produce membranes capable of water electrolysis at low cell voltages. It should be noted that MD refers to the mechanical direction of continuous forming, and TD refers to the direction orthogonal to MD.

[0149] In addition, a method can be cited as an example of producing porous membranes by melting and extruding polyethylene alone or a mixture of polyethylene and a nucleating agent, and then immediately stretching and orienting it in the uniaxial direction at a high draw ratio after extrusion, followed by heat treatment and stretching (the so-called dry method).

[0150] It should be noted that the manufacturing method of the polyethylene porous membrane in this embodiment is not limited to the above-described manufacturing method, and various modifications can be made without departing from its main idea.

[0151] [Mixed Process (a)]

[0152] Mixing step (a) is the process of mixing a resin composition containing polyethylene and a pore-forming material. It should be noted that other components may be mixed in mixing step (a) as needed.

[0153] The pore-forming material can be any material, as long as it is distinguishable from polyethylene and inorganic particles. Examples of pore-forming materials include non-volatile solvents that can form a homogeneous solution above the melting point of polyethylene, such as liquid paraffin, paraffin wax, and other hydrocarbons; esters such as dioctyl phthalate, dibutyl phthalate, and diisononyl phthalate; and higher alcohols such as oleyl alcohol and stearyl alcohol. It should be noted that these pore-forming materials can be recovered and reused after extraction through processes such as distillation.

[0154] Among pore-forming materials, liquid paraffin has high compatibility with polyethylene. Therefore, even if the molten compound is stretched, it is difficult to cause interfacial delamination between the resin and the pore-forming material. It also tends to be easy to perform uniform stretching, so it is preferred.

[0155] In step (a), the resin composition containing polyethylene may contain any additives. There are no particular limitations on the additives; examples include: polymers other than polyethylene; antioxidants such as phenolic compounds, phosphorus compounds, and sulfur compounds; metallic soaps such as calcium stearate and zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; coloring pigments; etc. The total amount of these additives added relative to 100 parts by weight of polyethylene is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, and even more preferably 5 parts by weight or less.

[0156] The mixing method in step (a) is not particularly limited. For example, methods such as using a Henschel mixer, ribbon mixer, or drum mixer to premix part or all of the raw materials as needed can be cited. Among these, the method of using a Henschel mixer for mixing is preferred.

[0157] Alternatively, one can choose to skip step (a) and supply each raw material individually to the next step (b). Examples include: supplying polyethylene and pore-forming material to the twin-screw extruder separately from individual feeders and liquid pumps; or preparing a mixture of polyethylene and any additives and supplying it, along with other components, to the twin-screw extruder from individual feeders.

[0158] [Extrusion process (b)]

[0159] Extrusion step (b) is a process in which a resin composition comprising polyethylene and a pore-forming material is melt-blended and extruded. It should be noted that in extrusion step (b), other components may be mixed with the resin composition as needed.

[0160] The method of melt mixing in step (b) is not particularly limited. For example, a method of melt mixing all the raw materials containing the mixture in step (a) can be described using a screw extruder such as a single screw extruder or a twin screw extruder; a kneader; a mixer, etc.

[0161] Melt mixing is preferably carried out using a screw in a twin-screw extruder.

[0162] The mass fraction of polyethylene in the resin composition comprising polyethylene and the pore-forming material is preferably 12% by mass or more and less than 40% by mass, more preferably 15% by mass or more and less than 35% by mass, and even more preferably 18% by mass or more and less than 33% by mass. If the mass fraction of polyethylene is less than 40% by mass, the energy during mixing will not rise excessively, and the molecular weight reduction caused by excessive entanglement of polymers can be suppressed, thus not impairing the properties of the polyethylene porous membrane. On the other hand, if the mass fraction of polyethylene is 12% by mass or more, sufficient energy can be imparted during melt mixing, and uniform mixing can be achieved through the entanglement of polymers. Therefore, even when the mixture of polyethylene and the pore-forming material is stretched at a high ratio, the entanglement of polyethylene molecular chains will not be unwound, and a uniform and fine pore structure is easily formed, and the mechanical strength is also easily increased.

[0163] Furthermore, during melt mixing, the pore-forming material can be added in one go using a dispensing pump, or it can be added separately from multiple locations using multiple dispensing pumps. When adding the additive in multiple stages, it is preferable to adjust the amount of the first addition to be less than 80% by mass of the total addition, in order to suppress the aggregation of polyethylene and inorganic particles and to achieve uniform dispersion.

[0164] As described above, by uniformly dispersing polyethylene and inorganic particles, the viscosity near the melting point of the porous membrane containing polyethylene is increased, making it less prone to pore blockage and promoting a reduction in cell voltage during alkaline water electrolysis, thus improving output characteristics. Furthermore, by uniformly dispersing polyethylene and inorganic particles, deviations in membrane properties are reduced. Therefore, even with a large-area membrane, performance deviations within the unit can be suppressed. Moreover, even when multiple units are combined to form a stack for electrolysis, performance deviations between individual units can be suppressed. Therefore, this method is preferred from the perspective of improving the uniformity of unit performance.

[0165] When a pore-forming material is used in step (b), from the perspective of dispersibility of polyethylene and suppression of molecular weight reduction, the temperature of the melt mixing section is preferably 250°C or lower, more preferably 230°C or lower, and even more preferably 210°C or lower. From the perspective of uniformly dissolving polyethylene in the pore-forming material, the lower limit of the temperature of the melt mixing section is preferably above the melting point of the polyethylene used.

[0166] In this embodiment, there are no particular limitations on the mixing process. Preferably, after mixing the antioxidant into the raw polyethylene at a predetermined concentration, the mixture is surrounded by a nitrogen atmosphere, and melt mixing is carried out while maintaining the nitrogen atmosphere. The temperature during melt mixing is preferably 160°C or higher, more preferably 180°C or higher, and preferably less than 300°C.

[0167] In step (b), the compound obtained by the above-described mixing process is extruded by an extruder such as a T-die, an annular die, or a slit nozzle. There are no particular limitations on the extrusion conditions; for example, known methods can be used. When a T-die is used to obtain the extrudate, from the perspective of easily controlling the thickness of the diaphragm in the final product, the slit gap of the die is preferably 1.2 mm to 7 mm, more preferably 1.5 mm to 6 mm, and even more preferably 2 mm to 5 mm. It is preferable to heat the die to 150°C to 250°C during extrusion.

[0168] In step (b), the moisture and volatile components contained in the raw materials are mixed into the melt-mixed compound during melt mixing, which may have an adverse effect on the compound extruded from the extruder. Therefore, it is preferable to have a degassing vent and a vacuum pump in the extruder to remove the moisture and volatile components that are vaporized during melt mixing.

[0169] [Sheet forming process (c)]

[0170] The sheet forming process (c) is a process of forming the extrudate obtained in the extrusion process (b) into a sheet shape. The sheet shape obtained by the sheet forming process (c) can be a single layer or a laminate, but a single layer is preferred. There is no particular limitation on the method of sheet forming; for example, a method of solidifying the extrudate by compression and cooling can be cited.

[0171] There are no particular limitations on the compression cooling method. For example, methods that bring the extrudate into direct contact with cooling media such as cold air or cooling water, or methods that bring the extrudate into contact with metal rollers or presses cooled by refrigerant, are all acceptable. However, from the perspective of easy control of film thickness, methods that bring the extrudate into contact with metal rollers or presses cooled by refrigerant are preferred.

[0172] After the melt-blending in step (b), the set temperature in the step of forming the melt into sheets is preferably set to the same as or higher than the set temperature of the extruder. From the perspective of the thermal degradation of polyethylene, the upper limit of the set temperature is preferably 300°C or less, more preferably 260°C or less, and even more preferably 240°C or less. For example, when continuously manufacturing sheet-shaped articles by an extruder, if the set temperature of the sheet-forming step after the melt-blending step, i.e., the path from the extruder outlet to the T-die, and the set temperature of the T-die are set to a high temperature higher than the set temperature of the extrusion step, the finely dispersed inorganic particles in the melt-blending step will no longer agglomerate, and the melt can be formed into sheets, which is therefore preferable. In particular, when inorganic particles with small average primary particle size are added, the effect of suppressing agglomeration is significant.

[0173] [Single stretching process (d)]

[0174] A single stretching process (d) is a process in which the sheet formed in the sheet forming process (c) is stretched at least once in at least one uniaxial direction. This stretching process (the stretching process performed before the subsequent extraction process (e)) is called "single stretching," and the film obtained through single stretching is called "single stretch film." In single stretching, the sheet formed can be stretched in at least one direction, either MD or TD, or only in either MD or TD. MD refers to the mechanical direction of continuous forming, and TD represents the direction orthogonal to MD.

[0175] The stretching method for a single stretching step is not particularly limited. Examples include uniaxial stretching using a roller stretching machine; TD uniaxial stretching using a tenter frame; sequential biaxial stretching using a combination of a roller stretching machine and a tenter frame, or multiple tenter frames; and simultaneous biaxial stretching using a simultaneous biaxial tenter frame or blow molding. Among these, sequential biaxial stretching or simultaneous biaxial stretching is preferred in order to achieve a balance between the ion permeability and mechanical strength of the obtained porous membrane.

[0176] The stretching ratio of the MD and / or TD in a single stretch is preferably 2 times or more, more preferably 3 times or more, and even more preferably 4 times or more. By making the stretching ratio of the MD and / or TD in a single stretch 2 times or more, the mechanical strength of the resulting porous membrane tends to be further improved. Furthermore, the stretching ratio of the MD and / or TD in a single stretch is preferably 10 times or less, more preferably 8 times or less, and even more preferably 6 times or less. By making the stretching ratio of the MD and / or TD in a single stretch 10 times or less, the tensile fracture tends to be further suppressed. When performing biaxial stretching, it can be sequential stretching or simultaneous biaxial stretching, and the stretching ratio in each axis is preferably 2 times or more and 10 times or less, more preferably 3 times or more and 8 times or less, and even more preferably 4 times or more and 6 times or less, respectively.

[0177] In simultaneous biaxial or sequential biaxial stretching during a single stretch, the tensile strain rate of MD and TD is preferably 0.5% / s to 50% / s, more preferably 1% / s to 45% / s, even more preferably 1.5% / s to 40% / s, and most preferably 2% / s to 35% / s. While not wishing to be bound by theory, it is speculated that if the tensile strain rate of MD and TD is 0.5% / s or higher, the polymers in the sheet-like molded body are stretched while remaining entangled, resulting in a porous membrane with high mechanical strength and uniform pore size, which can suppress the formation of large-pores that could lead to a decrease in gas purity during electrolysis. If the tensile strain rate of MD and TD is 50% / s or lower, the residual stress of the resulting polyethylene porous membrane is reduced, tending to reduce shrinkage, and is therefore preferred.

[0178] The stretching temperature is not particularly limited and can be selected with reference to the composition and concentration of the raw resins contained in the polyethylene resin composition. From the perspective of preventing breakage due to excessive tensile stress and balancing mechanical strength with thermal shrinkage, the stretching temperature is preferably within the range of 30°C lower than the melting point Tm of the porous membrane to the melting point Tm (Tm-30°C~Tm°C). In the case of the porous membrane of this embodiment, where 50% by mass or more of the porous membrane is PE, the stretching temperature is specifically preferably 100°C or higher, and from the perspective of improving the mechanical strength of the porous membrane, it is preferably 135°C or lower. Specifically, the stretching temperature is preferably 100°C~135°C, more preferably 110°C~130°C, and even more preferably 120°C~128°C.

[0179] [Extraction process (e)]

[0180] Extraction step (e) is a step of obtaining an extracted membrane by extracting the pore-forming material from the primary stretched membrane obtained in the primary stretching step (d). Methods for removing the pore-forming material include, for example, immersing the primary stretched membrane in an extraction solvent to extract the pore-forming material and then thoroughly drying it. The method for extracting the pore-forming material can be either batch or continuous. Furthermore, the residual amount of pore-forming material, particularly pore-forming material, in the porous membrane is preferably less than 1% by mass.

[0181] The extraction solvent used when extracting the pore-forming material is preferably a solvent that is a poor solvent relative to polyethylene but a good solvent relative to the pore-forming material or the pore-forming material itself, and has a boiling point lower than the melting point of polyethylene. There are no particular limitations on such extraction solvents; examples include: hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; non-chlorinated halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. It should be noted that these extraction solvents can be recovered and reused through operations such as distillation.

[0182] [Heat setting process (f)]

[0183] The heat setting process (f) is a process in which the extracted membrane obtained in the extraction process (e) is heat-set at a specified temperature. There are no particular limitations on the heat treatment method used at this time; examples include heat setting methods that utilize a tenter frame or a roll stretching machine for stretching and relaxation operations.

[0184] The stretching operation in the heat setting process (f) is an operation of stretching the porous membrane in at least one of the MD and TD directions. It can be performed in both the MD and TD directions, or only in one of the MD or TD directions.

[0185] In the heat setting process (f), the stretching ratios of MD and TD are preferably 1.0 times or more, more preferably 1.1 times or more, further preferably 1.2 times or more, and even more preferably 1.5 times or more. It should be noted that the upper limit of the stretching ratios of MD and TD in the heat setting process (f) is not particularly limited, but is preferably 2.5 times or less. If the stretching ratio is outside the above range, residual shrinkage stress near the melting point tends to worsen heat shrinkage. Furthermore, by making the stretching ratio within the above range, there is a tendency to further improve the mechanical strength and porosity of the porous membrane.

[0186] The stretching temperature during this stretching operation is not particularly limited, but is preferably at a temperature 30°C or lower than the melting point Tm of the porous membrane (i.e., stretching temperature ≥ Tm - 30°C), more preferably at a temperature 25°C or higher than the melting point Tm of the porous membrane, and even more preferably in the range from 20°C or higher than the melting point Tm of the porous membrane to the melting point Tm (i.e., Tm - 20°C to Tm). In the case of the porous membrane of this embodiment, where 50% by mass or more of the porous membrane is PE, the stretching temperature is specifically preferably 110°C or higher, and preferably 136°C or lower from the perspective of improving the mechanical strength of the porous membrane. Specifically, the stretching temperature is 110°C to 136°C, more preferably 115°C to 134°C, and even more preferably 120°C to 133°C. By keeping the stretching temperature within the above range, there is a tendency to further reduce the thermal shrinkage rate of the obtained porous membrane and further improve its porosity and mechanical strength.

[0187] The relaxation operation in the heat setting process (f) is an operation that shrinks the porous membrane in at least one of the MD and TD directions. It can be performed in both MD and TD directions, or only in one of the MD or TD directions. The relaxation rate in the heat setting process (f) is preferably 2% or more, more preferably 3% or more, further preferably 4% or more, and even more preferably 5% or more. By making the relaxation rate in the heat setting process (f) 2% or more, there is a tendency to improve the heat shrinkage rate. Furthermore, from the perspective of membrane quality, the relaxation rate is preferably 30% or less, and from the perspective of increasing the relaxation temperature, it is further preferably 25% or less. Here, "relaxation rate" refers to the value obtained by subtracting the size of the membrane after the relaxation operation from the size of the membrane before the relaxation operation, and dividing the result by the size of the membrane before the relaxation operation. In the case of relaxing both MD and TD, it is the value obtained by multiplying the relaxation rate of MD by the relaxation rate of TD.

[0188] Relaxation rate (%) = (Membrane size before relaxation (m) - Membrane size after relaxation (m)) / (Membrane size before relaxation (m)) × 100

[0189] The relaxation ratio in the heat setting process (f) is not particularly limited, but is preferably 1.0 to 1.8 times, more preferably 1.1 to 1.7 times, and even more preferably 1.2 to 1.6 times. By making the relaxation ratio in the heat setting process (f) 1.0 times or more, the tank voltage becomes good, and by making it 1.8 times or less, excessive enlargement of the pore size can be suppressed. Here, the relaxation ratio refers to the value obtained by dividing the size of the film after the relaxation operation by the size of the film before stretching.

[0190] The relaxation temperature in this relaxation operation is not particularly limited. In order to obtain the porous membrane of this embodiment and the alkaline water electrolysis diaphragm containing the porous membrane, it is preferable that the melting point of the porous membrane is below Tm, more preferably that it is in the range from the temperature of the porous membrane melting point Tm-7°C to the temperature of the melting point Tm (i.e., Tm-7°C to Tm), and even more preferably that it is in the range from the temperature of the porous membrane melting point Tm-6°C to the temperature of the melting point Tm-2°C (i.e., Tm-6°C to Tm-2°C).

[0191] By keeping the temperature during the relaxation operation within the above-mentioned range, not only can the residual stress from the stretching process be removed, but the orientation of the molecular chains can also be firmly fixed. Therefore, it is preferred from the perspective of preventing the reduction of ion permeability near the melting point of the porous membrane and improving the performance of electrochemical devices.

[0192] (Electrolytic cell for alkaline water electrolysis)

[0193] The electrolytic cell for alkaline water electrolysis in this embodiment is an electrolytic cell that includes the diaphragm, anode, and cathode described in this embodiment, with the diaphragm disposed between the anode and the cathode.

[0194] Hereinafter, an example of an alkaline water electrolysis cell of this embodiment, which includes a cathode, an anode, and a diaphragm, will be described with reference to the accompanying drawings.

[0195] It should be noted that the electrolytic cell for alkaline water electrolysis in this embodiment is not limited to the electrolytic cell described below. In addition, the components included in the electrolytic cell for alkaline water electrolysis, other than the anode, cathode and diaphragm, are not limited to the components listed below, and known components can be appropriately selected and designed for use.

[0196] The alkaline water electrolysis cell of this embodiment is a bipolar electrolysis cell formed by laminating (stacking) the alkaline water electrolysis diaphragm of this embodiment and a bipolar element holding a cathode and an anode. In other words, the alkaline water electrolysis cell of this embodiment is a bipolar electrolysis cell that includes a combination (also called an "electrolysis unit") of multiple anodes, cathodes, and the alkaline water electrolysis diaphragm of this embodiment disposed between the anodes and cathodes.

[0197] The diaphragm for alkaline water electrolysis of this embodiment is characterized by having a porous membrane containing 50% by mass or more of polyethylene resin and having a tortuosity of 3.00 or less. This diaphragm can ensure good airtightness of the electrolytic cell even when using sheet-like gaskets, and can perform water electrolysis at a low cell voltage.

[0198] Thus, the characteristic of the bipolar electrolyzer for alkaline water electrolysis of this embodiment is that it includes the diaphragm for alkaline water electrolysis of this embodiment described above; other than this, there are no particular limitations on the configuration. Hereinafter, an example of the configuration of the bipolar electrolyzer for alkaline water electrolysis of this embodiment will be described with reference to the accompanying drawings.

[0199] Figure 1 This is a side view showing an example of a bipolar electrolyzer for alkaline water electrolysis according to this embodiment.

[0200] Figure 2 A zero-gap structure is shown for an example of the bipolar electrolyzer for alkaline water electrolysis in this embodiment. Figure 1 The side view of the portion within the dashed box shown.

[0201] Figure 3 This is a top view showing an example of the electrode chamber portion of the bipolar electrolyzer for alkaline water electrolysis according to this embodiment.

[0202] like Figure 1As shown, the bipolar electrolyzer for alkaline water electrolysis in this embodiment is a bipolar electrolyzer 50, which is formed by overlapping a plurality of electrolysis units 65, including an anode 2a, a cathode 2c, a partition wall 1 that isolates the anode 2a and the cathode 2c, and an outer frame 3 that edges the partition wall 1, with a diaphragm 4 sandwiched between them.

[0203] In this embodiment of the alkaline water electrolysis bipolar electrolyzer, there are no particular limitations, but it is preferable to form a zero-gap structure Z in which the diaphragm 4 contacts the anode 2a and the cathode 2c (see reference). Figure 2 ).

[0204] Furthermore, in the bipolar electrolytic cell 50 of this embodiment, the electrode chamber 5 through which the electrolyte passes is divided by the partition wall 1, the outer frame 3, and the diaphragm 4. Multiple rectifier plates 6 (see reference 1) are arranged in the electrode chamber 5 parallel to a predetermined direction D1 along the partition wall 1. Figure 2 , Figure 3 ).

[0205] like Figures 2-3 As shown, in one example, the bipolar element 60 used in a bipolar electrolyzer for alkaline water electrolysis includes a partition 1 that isolates the anode 2a from the cathode 2c, and an outer frame 3 that edges the partition 1. More specifically, the partition 1 is conductive, and the outer frame 3 is configured to surround the partition 1 along its outer edge.

[0206] It should be noted that, in this embodiment, the bipolar element 60 can typically be used in a vertical manner along the predetermined direction D1 of the partition wall 1. Specifically, as... Figure 2 , Figure 3 As shown, when the top view of partition 1 is rectangular, it can be used in a manner where the predetermined direction D1 of partition 1 is the same as the direction of one of the two sets of opposing sides (see reference). Figures 1-3 Furthermore, in this specification, the aforementioned vertical direction is also referred to as the electrolyte flow direction.

[0207] In this embodiment, such as Figure 1 As shown, the bipolar electrolytic cell 50 is constructed by laminating the required number of bipolar elements 60.

[0208] exist Figure 1In one example shown, the bipolar electrolytic cell 50 is arranged sequentially from one end with a fastening head 51g, an insulating plate 51i, and an anode terminal element 51a. Then, an anode-side gasket portion 7, a diaphragm 4, a cathode-side gasket portion 7, and a bipolar element 60 are arranged sequentially. At this time, the bipolar element 60 is arranged with the cathode 2c facing the anode terminal element 51a. The bipolar element 60 is repeatedly arranged from the anode-side gasket portion 7 to the bipolar element 60 according to the required production quantity. After repeating the bipolar element 60 from the anode-side gasket portion 7 to the bipolar element 60 in the required quantity, the anode-side gasket portion 7, the diaphragm 4, and the cathode-side gasket portion 7 are arranged again, and finally, the cathode terminal element 51c, the insulating plate 51i, and the movable head 51g are arranged sequentially. The entire bipolar electrolytic cell 50 is connected by a pull rod 51r (see reference). Figure 1 It is fastened by fastening mechanisms such as hydraulic cylinders and integrated into a bipolar electrolytic cell 50.

[0209] The configuration of the bipolar electrolytic cell 50 can be arbitrarily selected from either the anode 2a side or the cathode 2c side, and is not limited to the above order.

[0210] like Figure 1 As shown, in the bipolar electrolytic cell 50, the bipolar element 60 is disposed between the anode terminal element 51a and the cathode terminal element 51c, and the diaphragm 4 is disposed between the anode terminal element 51a and the bipolar element 60, between adjacent bipolar elements 60, and between the bipolar element 60 and the cathode terminal element 51c.

[0211] Furthermore, in the bipolar electrolytic cell 50 of this embodiment, such as Figure 2 , Figure 3 As shown, the electrode chamber 5 through which the electrolyte passes is divided by the partition wall 1, the outer frame 3, and the diaphragm 4.

[0212] In detail, the electrode chamber 5 has an electrolyte inlet for introducing electrolyte into the electrode chamber 5 and an electrolyte outlet for discharging electrolyte from the electrode chamber 5 at its boundary with the outer frame 3. More specifically, the anode chamber 5a is provided with an anolyte inlet for introducing electrolyte into the anode chamber 5a and an anolyte outlet for discharging electrolyte discharged from the anode chamber 5a, and the cathode chamber 5c is provided with a cathode electrolyte inlet for introducing electrolyte into the cathode chamber 5c and a cathode electrolyte outlet for discharging electrolyte discharged from the cathode chamber 5c.

[0213] It should be noted that, in Figures 1-3 In the example shown, the rectangular partition 1 is arranged parallel to the rectangular diaphragm 4. In addition, the inner surface of the cuboid-shaped outer frame 3 located at the end edge of the partition 1 is perpendicular to the partition 1, so the electrode chamber 5 is cuboid in shape.

[0214] The bipolar electrolyzer 50 is typically equipped with pipes, i.e., manifolds, for distributing or collecting electrolyte. Below the outer frame 3 located at the end edge of the partition wall 1, there is an anode inlet manifold for the electrolyte to enter the anode chamber 5a and a cathode inlet manifold for the electrolyte to enter the cathode chamber 5c. Similarly, above the outer frame 3 located at the end edge of the partition wall 1, there is an anode outlet manifold for the electrode solution to flow out of the anode chamber 5a and a cathode outlet manifold for the electrolyte to flow out of the cathode chamber 5c.

[0215] It should be noted that, as installed in Figures 1-3 The configuration of the manifold of the bipolar electrolytic cell 50 shown can be represented by internal manifold type and external manifold type. In this invention, any type can be used without particular limitation.

[0216] In the bipolar electrolytic cell 50 of this embodiment, the electrolyte distributed by the anode inlet manifold is introduced into the anode chamber 5a through the anode electrolyte inlet, passes through the anode chamber 5a, is discharged from the anode chamber 5a through the anode electrolyte outlet, and is collected by the anode outlet manifold.

[0217] And, as Figure 2 , Figure 3 As shown, the electrode chamber in this embodiment has a plurality of rectifier plates 6 arranged parallel to a predetermined direction D1 along the partition wall 1.

[0218] The rectifier plate 6 reduces convection in the electrode chamber 5 caused by turbulence in the gas-liquid flow, thus suppressing the local temperature rise of the electrolyte.

[0219] In particular, Figures 1-3 In the example shown, multiple rectifier plates 6 are arranged at certain intervals (spacing) in a direction perpendicular to the predetermined direction (in the example shown, the direction of electrolyte passage) D1 along the partition wall 1.

[0220] In another example, in a bipolar electrolyzer 50, the rectifier plate 6 has a length approximately the same as the height of the electrode chamber 5, is arranged perpendicularly to the partition wall 1, and has through holes at predetermined intervals along a predetermined direction D1 (the direction of electrolyte passage in the illustrated example) of the partition wall 1.

[0221] It should be noted that, in this invention, the shape of the electrode chamber 5 is not limited to... Figures 1-3 The cuboid shown in the example can be appropriately deformed according to the top view shape of the partition 1 and the diaphragm 4, the angle between the inner surface of the partition 2 side of the outer frame 3 and the partition 2, etc. As long as the effect of the present invention can be obtained, it can be any shape.

[0222] It should be noted that, in this invention, the arrangement of the rectifier plate 6 in the electrode chamber 5 is not limited to... Figures 1-3 The example shown.

[0223] Furthermore, in this invention, the number of rectifier plates 6 and the spacing (pitch) between the rectifier plates 6 and the direction perpendicular to the predetermined direction D1 along the partition wall 1 can be appropriately determined as long as the effects of this invention are achieved. Here, the spacing of the rectifier plates 6 may also be flexible.

[0224] Furthermore, in this invention, the length of the rectifier plate 6, the angle between the rectifier plate 6 and the partition wall 1, the number of through holes, and the certain interval (spacing) of the through holes along the predetermined direction D1 of the partition wall 1 can be appropriately determined as long as the effects of this invention are achieved. Here, the interval of the through holes may also be flexible.

[0225] It should be noted that, in Figures 1-3 In the example shown, the partition 1, anode 2a, and cathode 2c are all plate-shaped with a specified thickness, but the present invention is not limited to this. They can be wholly or partially serrated or wavy in cross-section, or they can be rounded at the ends.

[0226] [Diaphragm for alkaline water electrolysis]

[0227] The diaphragm 4 used in the alkaline water electrolysis cell of this embodiment is the alkaline water electrolysis diaphragm of the present invention described above, and the description is omitted.

[0228] [Electrodes (anode, cathode)]

[0229] In the alkaline water electrolysis reaction, alkaline water is electrolyzed in an electrolytic cell equipped with an electrode pair (i.e., an anode and a cathode) connected to a power source, producing oxygen at the anode and hydrogen at the cathode.

[0230] The electrode 2 included in the bipolar electrolyzer 50 for alkaline water electrolysis of this embodiment will be described in detail below.

[0231] It should be noted that, in this specification, the term "electrode" refers to either or both of the anode 2a and the cathode 2c.

[0232] In the case of a zero-gap electrolytic cell described later, it is necessary to degas the gas generated from the back side of the contact surface with the diaphragm 4. Therefore, it is preferable that the porous electrode is located on the side opposite to the contact surface with the diaphragm 4.

[0233] The porous electrode in this embodiment is not particularly limited. From the perspective of controlling the average pore size, electrodes with mesh (grid) structures such as plain weave type, perforated type, and expanded type, as well as metal foams, can be cited. Among them, from the perspective of controlling the size and shape of the pores, a mesh structure selected from the group consisting of plain weave type, perforated type, and expanded type is preferred.

[0234] In this embodiment, the porous electrode can be the substrate itself, or it can have a highly reactive catalyst layer on the surface of the substrate, but it is preferred to have a highly reactive catalyst layer on the surface of the substrate.

[0235] There are no particular limitations on the material used as the substrate, and examples include conductive substrates composed of at least one selected from the group consisting of nickel, iron, low-carbon steel, stainless steel, vanadium, molybdenum, copper, silver, manganese, platinum group metals, graphite, and chromium. Conductive substrates composed of alloys of two or more metals or mixtures of two or more conductive substances may also be used. Among these, nickel and nickel-based alloys are preferred from the perspectives of substrate conductivity and resistance to the operating environment.

[0236] Methods for forming a catalyst layer on a substrate include plating, plasma spraying, thermal decomposition by applying a precursor solution to the substrate and then heating it, mixing the catalyst material with a binder component and fixing it to the substrate, and vacuum film formation methods such as sputtering.

[0237] In the zero-gap structure described later, the diaphragm 4 is pressed more firmly against the electrode than in conventional electrolysis units. For example, in electrodes using expanded substrates, the diaphragm 4 may sometimes break at the end of the opening, or the diaphragm 4 may become trapped in the opening, creating a gap between the cathode 2c and the diaphragm 4, resulting in a voltage increase.

[0238] To address the aforementioned issues, it is preferable to design the electrode shape as planar as possible. For example, the following method can be used: pressing the expanded substrate (e.g., an expanded substrate) with a roller to form a planar shape. In this case, it is preferable to press the substrate to a thickness of 95% to 110% relative to the original metal plate thickness before the expansion process to achieve planarization.

[0239] The electrode 2 manufactured by performing the above treatment not only prevents damage to the diaphragm 4, but also surprisingly reduces the voltage. The reason for this is not yet clear, but it is presumed that the current density is uniformly uniform because the surface of the diaphragm 4 is in uniform contact with the electrode surface.

[0240] The size of electrode 2 is not particularly limited and can be determined based on the shape and size of the bipolar electrolyzer, electrolysis unit, bipolar element, partition, etc., used for alkaline water electrolysis, or based on the desired electrolysis capacity. For example, if the partition is plate-shaped, the size can be determined based on the dimensions of the partition.

[0241] [Gasket]

[0242] In the alkaline water electrolysis bipolar electrolyzer 50 of this embodiment, preferably the sealing area (edge) of the diaphragm 4 and the bipolar element 60 are further stacked with a gasket 7 in between.

[0243] The gasket 7 is used to seal the electrolyte and generated gas between the bipolar element 60 and the diaphragm 4, and between the bipolar elements 60, so as to prevent the electrolyte and generated gas from leaking to the outside of the unit and the gas from mixing between the two electrode chambers.

[0244] There are no particular restrictions on the material of gasket 7; known insulating materials such as rubber and resin can be selected.

[0245] Specifically, rubber and resin materials that can be used include natural rubber (NR), styrene-butadiene rubber (SBR), chloroprene rubber (CR), butadiene rubber (BR), acrylonitrile-butadiene rubber (NBR), silicone rubber (SR), ethylene-propylene rubber (EPT), ethylene propylene diene monomer (EPDM), fluororubber (FR), isobutylene-isoprene rubber (IIR), polyurethane rubber (UR), and chlorosulfonated PE rubber (CSM); fluoropolymers such as polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-ethylene copolymer (ETFE), and trifluorochloroethylene-ethylene copolymer (ECTFE); and resins such as polyphenylene sulfide (PPS), PE, polyimide, and polyacetal. Among these, ethylene propylene diene monomer (EPDM) and fluororubber (FR) are particularly preferred in terms of elastic modulus and alkali resistance.

[0246] The gasket 7 may be embedded with reinforcing material. Therefore, when it is clamped and pressed by the frame during stacking, the gasket 7 can be prevented from being crushed, and breakage can be easily prevented.

[0247] Such reinforcing materials can use known metal materials, resin materials, and carbon materials. Specifically, examples include metals such as nickel and stainless steel, resins such as nylon, polypropylene, PVDF, PTFE, and PPS, and carbon materials such as carbon particles and carbon fibers.

[0248] The preferred shape for the reinforcing material is woven fabric, nonwoven fabric, short fiber, or porous membrane. Furthermore, a protective layer can be provided on the surface of the gasket 7. This improves the seal between the gasket 7 and the component, and also enhances the alkali resistance of the gasket 7. The material for this protective layer can be selected from the material of the gasket 7.

[0249] There are no particular restrictions on the size of the gasket 7, as long as it is designed to match the size of the electrode chamber 5 and the membrane, but the width is preferably 10mm to 40mm.

[0250] The thickness of the gasket 7 is not particularly limited and is designed based on the material, elastic modulus, and unit area of ​​the gasket 7. As a preferred thickness range, it is preferably 1 mm to 10 mm, and more preferably 1.5 mm to 10 mm.

[0251] Furthermore, the shape of the gasket 7 is not particularly limited, but it is preferably designed according to the shape of the bipolar element 60. From the perspective of good operability when assembling the electrolytic cell 50, it is preferred to be sheet-shaped, and more preferably a sheet-shaped structure (frame shape) that contacts the outer periphery (outer frame 3) of the bipolar element 60. By adopting a structure in which the diaphragm 4 is sandwiched between two gaskets 7 on the outer periphery (outer frame 3) of the bipolar element 60 (the diaphragm 4 sandwiched between two gaskets 7 is sandwiched between the outer periphery (outer frame 3) of the bipolar element 60), both the assembly operability and airtightness of the electrolytic cell 50 can be taken into account.

[0252] That is, the electrolytic cell for alkaline water electrolysis in this embodiment is preferably the following electrolytic cell, which includes the alkaline water electrolysis diaphragm, sheet gaskets, anode, and cathode described in this embodiment, with the alkaline water electrolysis diaphragm disposed between the anode and the cathode. Furthermore, the electrolytic cell for alkaline water electrolysis in this embodiment is preferably the following electrolytic cell, which includes the alkaline water electrolysis diaphragm, two sheet gaskets, anode, and cathode described in this embodiment, with the alkaline water electrolysis diaphragm disposed between the anode and the cathode, and the two sheet gaskets arranged to clamp the alkaline water electrolysis diaphragm.

[0253] Furthermore, when the gasket 7 has a quadrilateral slit structure (a U-shaped cross-section) capable of accommodating the diaphragm 4, the spacing between the slit portions into which the diaphragm 4 is inserted is preferably 0.2 mm to 1.2 mm or less, preferably 0.25 mm to 1.1 mm or less, more preferably 0.3 mm to 1.0 mm or less, and even more preferably 0.35 mm to 0.8 mm or less. Additionally, the depth to which the slit portion of the diaphragm 4 is inserted into the slit structure is preferably 4.0 mm to 90 mm or less, more preferably 4.5 mm to 85 mm or less, and even more preferably 5.0 mm to 80 mm or less.

[0254] In addition, there is no particular limitation on the height of the protrusion when the above-mentioned protrusion is provided, but it is preferable to be 0.5mm to 5mm in order to show sufficient pressing pressure.

[0255] The elastic modulus of the gasket 7 is not particularly limited and is designed according to the material of the electrode 2 and the unit area. As a preferred range of elastic modulus, measured by tensile stress at 100% deformation, it is more preferably in the range of 0.20 MPa to 20 MPa, and from the perspective of sealing characteristics and unit strength during stacking, it is more preferably in the range of 1.0 MPa to 10 MPa.

[0256] It should be noted that tensile stress can be measured according to JIS K6251. For example, the Autograph AG manufactured by Shimadzu Corporation can be used.

[0257] When installing the gasket 7 onto the bipolar element 60, an adhesive can also be used. Adhesive can be applied to one side of the gasket 7 and attached to one side of the outer frame 3 of the element. It should be noted that it is preferable to pre-wet the electrode 2 by adding water to the electrode surface of the bipolar alkaline water bipolar element 60 after the adhesive has dried. When the gasket 7 has a slit portion that accommodates the edge of the diaphragm 4 in a manner that can hold the diaphragm 4, the gasket can be attached while holding the diaphragm 4, or the diaphragm 4 can be held after attachment.

[0258] [Zero-gap structure]

[0259] In this embodiment of the alkaline water electrolysis bipolar electrolyzer 50, there are no particular limitations, such as... Figure 2 As shown, a so-called "zero-gap structure" Z is preferably formed in which the diaphragm 4 contacts the anode 2a and the cathode 2c. The "zero-gap structure" Z is a structure that can maintain the following state: the anode 2a and the diaphragm 4 are in contact with each other on the entire surface of the electrode, and the cathode 2c is in contact with the diaphragm 4; or, the distance between the electrodes is approximately the same as the thickness of the diaphragm 4 on the entire surface of the electrode, and there is almost no gap between the anode 2a and the diaphragm 4 and between the cathode 2c and the diaphragm 4.

[0260] In alkaline water electrolysis, when there is a gap between the diaphragm 4 and the anode 2a and cathode 2c, a large number of bubbles generated during electrolysis remain in this part in addition to the electrolyte, resulting in very high resistance.

[0261] On the other hand, if a zero-gap structure Z is formed, by rapidly discharging the generated gas through the fine holes of electrode 2 to the side of electrode 2 opposite to the diaphragm 4, it is possible to reduce the gap between anode 2a and cathode 2c (hereinafter also referred to as "inter-electrode distance") while suppressing voltage loss caused by electrolyte and gas accumulation near the electrode, thus suppressing the electrolysis voltage to a low level.

[0262] Several methods have been proposed to construct the zero-gap structure Z. For example, one method is to process the anode 2a and cathode 2c completely smoothly and press them together with the diaphragm 4; another method is to place an elastic body such as a spring between the electrode 2 and the diaphragm 4 and use the elastic body to support the electrode 2.

[0263] It should be noted that the preferred embodiment of the means of constructing the zero-gap structure Z in the alkaline water electrolysis bipolar electrolyzer 50 of this embodiment will be described later.

[0264] In the bipolar element 60 of the zero-gap type unit, as a means of reducing the inter-electrode distance, it is preferable to use a spring, which is an elastic body, disposed between the electrode 2 and the partition wall 1, and to support the electrode 2 with this spring. For example, in the first example, a spring made of conductive material can be installed on the partition wall 1, and the electrode 2 can be mounted on this spring. In the second example, a spring can be installed on the electrode rib 6 installed on the partition wall 1, and the electrode 2 can be mounted on this spring. It should be noted that when using this elastic body method, in order to avoid uneven pressure between the electrode 2 and the diaphragm 4, it is necessary to adjust it appropriately according to the strength, number, and shape of the spring.

[0265] Furthermore, by enhancing the rigidity of the other electrode 2 in a pair supported by an elastomer (for example, making the rigidity of the anode stronger than that of the cathode), a structure with minimal deformation even when pressed is formed. On the other hand, for the electrode 2 supported by the elastomer, by forming a flexible structure that deforms when the diaphragm 4 is pressed, unevenness caused by tolerances in the manufacturing precision of the electrolytic cell 50, deformation of the electrode 2, etc., can be absorbed to maintain a zero-gap structure Z.

[0266] In the alkaline water electrolysis bipolar electrolyzer 50 of this embodiment, such as Figure 2 As shown, between the cathode 2c or anode 2a and the partition wall 1, the conductive elastomer 2e and the current collector 2r are arranged such that the conductive elastomer 2e is sandwiched between the cathode 2c or anode 2a and the current collector 2r.

[0267] (Alkaline water electrolysis device)

[0268] Figure 4 An example of an alkaline water electrolysis apparatus that can use the bipolar electrolyzer for alkaline water electrolysis of this embodiment is shown.

[0269] Based on the bipolar electrolyzer 50 for alkaline water electrolysis in this embodiment, the alkaline water electrolysis device 70 may also include, in addition to the liquid delivery pump 71, gas-liquid separator 72, and water supply device 73, a rectifier 74, an oxygen concentration meter 75, a hydrogen concentration meter 76, a flow meter 77, a pressure gauge 78, a heat exchanger 79, and a pressure control valve 80.

[0270] (Alkaline water electrolysis)

[0271] Electrolysis is performed by circulating the electrolyte in an alkaline water electrolysis apparatus equipped with the bipolar electrolyzer for alkaline water electrolysis of this embodiment. Even under conditions of high-density current operation or fluctuating power supply operation, excellent electrolysis efficiency and high purity of generated gas can be maintained, thus achieving highly efficient alkaline water electrolysis.

[0272] The electrolyte that can be used for alkaline water electrolysis in this embodiment can be an alkaline aqueous solution containing an alkali metal salt, such as NaOH aqueous solution or KOH aqueous solution.

[0273] The concentration of the alkali metal salt is not particularly limited, but is preferably 20% to 50% by mass, more preferably 25% to 40% by mass. Among these, a KOH aqueous solution of 25% to 40% by mass is particularly preferred from the perspectives of ionic conductivity, kinematic viscosity, and freezing at low temperatures.

[0274] The temperature of the electrolyte in the electrolysis unit is not particularly limited, but is preferably 60°C to 100°C.

[0275] If the temperature is set within the above range, it is possible to effectively suppress the deterioration of components of the electrolysis device, such as gaskets and diaphragms, due to heat while maintaining high electrolysis efficiency.

[0276] The temperature of the electrolyte is further preferably 65℃~95℃, and particularly preferably 70℃~90℃.

[0277] In the alkaline water electrolysis of this embodiment, the current density provided to the electrolysis unit is not particularly limited, but is preferably 3 kA / m. 2 ~20kA / m 2 Further preferred is 6kA / m 2 ~15kA / m 2 Especially when using fluctuating power supplies, it is preferable to set the upper limit of the current density to the range mentioned above.

[0278] In the alkaline water electrolysis of this embodiment, the pressure within the electrolysis unit is not particularly limited, but is preferably 3 kPa to 1000 kPa, and more preferably 3 kPa to 300 kPa.

[0279] The flow rate of electrolyte and other conditions in each electrode chamber can be appropriately controlled according to the various components of the bipolar electrolyzer for alkaline water electrolysis.

[0280] The above description, with reference to the accompanying drawings, illustrates an alkaline water electrolysis bipolar electrolyzer according to an embodiment of the present invention. However, the alkaline water electrolysis bipolar electrolyzer of the present invention is not limited to the above examples, and appropriate modifications can be made to the above embodiments.

[0281] Example

[0282] The following describes embodiments of the present invention, but these embodiments are merely illustrative of the invention and do not limit the invention in any way.

[0283] [Methods for Determining and Evaluating Physical Properties]

[0284] The analytical and evaluation methods used in the examples and comparative examples are described below. It should be noted that (1) to (3) and (6) were all measured without filling the pores of the porous membrane with water.

[0285] (1) Film thickness (μm)

[0286] A porous membrane was cut out with MD10cm×TD10cm. Nine points (3 points×3 points) were selected in a grid pattern. The thickness was measured at room temperature (23°C) using a digital display indicator (Mitutoyo Co., Ltd., Code No. 543-390B). The average value of the nine measurements was taken as the membrane thickness.

[0287] (2) Porosity (%)

[0288] A 10cm × 10cm square sample is cut from the porous membrane, and its volume (cm³) is calculated. 3 ) and mass (g), based on them and membrane density (g / cm³) 3 The porosity can be calculated using the following formula.

[0289] Volume (cm) 3 )=10(cm)×10(cm)×film thickness (cm)

[0290] Porosity (%) = (Volume - Mass / Film Density) × 100 / Volume

[0291] It should be noted that, regarding the membrane density, the porous membrane or the resin used as raw material is heated to above the melting point using a hot press, then pressed into a sheet, cut to a certain size (e.g., 10cm × 10cm), the membrane thickness is measured to calculate the sheet volume, and the sheet mass is measured and calculated using the following formula.

[0292] Membrane density (g / cm³) 3 = Tablet mass (g) / Tablet volume (cm³) 3 )

[0293] (3) Air permeability (seconds) and air permeability (seconds) converted to 100μm thickness.

[0294] The following was used: a digital Wangyan-type air permeability testing machine (model EG01, measuring nozzle diameter 12.82 mm) conforming to JIS P-8117:2009. (mm, manufactured by Asahi Seiko Corporation) The time (in seconds) for 100 mL of air to pass through was measured and taken as the air permeability (in seconds) of the porous membrane. Based on the obtained air permeability, the air permeability converted to a thickness of 100 μm was obtained using the following formula.

[0295] Air permeability (seconds) for a 100μm thickness = (Air permeability (seconds) / Membrane (μm)) × 100

[0296] The test samples were cut from the porous membranes of the examples or comparative examples, measuring 10 cm × 10 cm, and approximately 4 points were measured at roughly equal intervals. The average value was used.

[0297] (4) Water permeability (g / 2 minutes)

[0298] The test samples were cut from the porous membrane to a size of 10 cm × 10 cm. The porous membrane, pre-soaked in ethanol for 1 minute, was placed in a 41 mm diameter stainless steel permeation unit (Advantec UltraHolder UHP-43K, stirred type). After rinsing the membrane with distilled water to remove the ethanol, distilled water was permeated for 2 minutes under a differential pressure (inside and outside the permeation unit) of approximately 50,000 Pa. After 2 minutes, the mass of the permeated water was recorded as the permeate volume (g / 2 minutes). The differential pressure was measured by connecting a portable pressure gauge (NIDEC COMPONENTS PG-100-102GP) to the pressurized side of the permeation unit.

[0299] (5) Tortuosity

[0300] According to the air permeability constant R gas (m 3 / (m 2 (·second·Pa) and the water permeability constant R liq (m 3 / (m 2 (·second·Pa)), air molecular velocity ν (m / s), water viscosity η (Pa·second), standard pressure P s (=101325Pa), porosity ε (%), film thickness L (μm), and pore diameter d (μm) and tortuosity τ (dimensionless) are calculated using the following formula.

[0301] d=2ν×(R liq / R gas )×(16η / 3P s )×10 6

[0302] τ=(d×(ε / 100)×ν / (3L×P s ×R gas )) 1 / 2

[0303] Here, R gas The air permeability (in seconds) can be calculated using the following formula.

[0304] R gas =0.0001 / (breathability × (6.424 × 10) -4 )×(0.01276×101325))

[0305] Rliq The permeability (g / 2 min) measured above and the area S (cm²) of the permeation unit used in the measurement are used as the basis for this determination. 2 Measurement time (120 seconds), differential pressure P during measurement gap (Pa) can be obtained using the following formula.

[0306] It should be noted that the specific gravity of the distilled water used is set to 1 g / cm³. 3 S is calculated from the diameter of the liquid permeation unit, which is 4.1 cm, used in the above water permeability measurement.

[0307] R liq = Permeability / (S×120×P) gap ) / 100

[0308] Additionally, ν is determined by the gas constant R (=8.314), absolute temperature T (K), pi (π), and the average molecular weight of air M (=2.896×10⁻⁶). -2 The weight (kg / mol) can be calculated using the following formula.

[0309] ν=((8R×T) / (π×M)) 1 / 2

[0310] (6) Puncture strength (gf)

[0311] A puncture testing machine, NDG5 (manufactured by KATO TECH), was used to fix a porous membrane using a sample holder with an opening diameter of 11.3 mm. A puncture test was performed on the central portion of the fixed porous membrane at a needle tip radius of curvature of 0.5 mm and a puncture speed of 2 mm / s in an atmosphere at 25°C. The puncture strength (gf) was measured as the maximum puncture load, and the puncture strength per 100 μm membrane thickness (gf / 100 μm) was calculated.

[0312] It should be noted that the determination of water permeability and puncture strength involves deformation of the porous membrane; therefore, the test pieces are only used for their respective determinations. The same test pieces are used for the determination of membrane thickness, porosity, air permeability, and the water electrolysis evaluation described later.

[0313] [Evaluation of Water Electrolysis]

[0314] The following describes the single-pole electrolyzer and electrolysis system used for water electrolysis evaluation.

[0315] [Monopolar Electrolyzer]

[0316] A bipolar electrolytic cell consists of an anode terminal element, a cathode terminal element, and multiple bipolar elements, such as... Figure 1While the electrolytic cell has a bipolar zero-gap structure, this evaluation uses a unipolar electrolytic cell consisting of anode terminal elements and cathode terminal elements. The anode, cathode, and diaphragm of each embodiment and comparative example are assembled in the same way in each electrolytic cell. The manifold of the electrolytic cell is configured as an external manifold type.

[0317] The electrodes (anode and cathode) used in the water electrolysis evaluation are fabricated as follows. The diaphragm used is the diaphragm fabricated in the examples and comparative examples.

[0318] <Anode>

[0319] As the anode, a nickel-expanded substrate is used with a center-to-center distance (LW) of 4.6 mm in the long axis direction, a center-to-center distance (SW) of 3.1 mm in the short axis direction, and a substrate thickness of 1.3 mm.

[0320] <Cathode>

[0321] An electrode prepared according to the following steps is used as the cathode.

[0322] As a conductive substrate, a 40-mesh plain weave grid-type substrate is used, made of nickel wire with a diameter of 0.15 mm. The substrate is sandblasted using alumina powder with a weight-average particle size of less than 100 μm, followed by acid treatment in 6N hydrochloric acid at room temperature for 5 minutes, and then washed with water and dried.

[0323] <Conductive Elastomers>

[0324] The conductive elastomer is made by weaving a fabric of 0.15mm diameter nickel wire with a corrugated pattern of 5mm wave height. It has a thickness of 5mm and a resilience of 150g / cm² at 50% compression. 2 The mesh size is approximately 5 meshes.

[0325] <Component>

[0326] The element is rectangular, measuring 70mm x 90mm, with the anode and cathode areas measuring 48mm x 58mm. Both the anode and cathode chambers have a depth of 10mm and are made of nickel. A nickel anode support with a height of 9mm and a diameter of 10mm is welded to the anode terminal element, and a nickel current collector support with a height of 6mm and a diameter of 10mm is welded to the cathode terminal element.

[0327] As a current collector, a nickel-expanded metal mesh with a thickness of 1.3 mm, a lateral length of 4.6 mm, and a longitudinal length of 3.1 mm is used. This current collector is fixed to the current collector support of the cathode terminal element using nickel screws. A conductive elastomer is placed on the current collector, and the cathode is placed on the conductive elastomer. Next, the anode is fixed to the anode support of the anode terminal element using nickel screws. Then, the cathode-side element and the anode-side element are stacked with a 70 mm × 90 mm diaphragm and two sheet-like EPDM gaskets with an outer dimension of 90 mm × 70 mm and an inner dimension of 70 mm × 50 mm sandwiched between them, thereby forming a zero-gap structure where the cathode and anode are pressed against the diaphragm.

[0328] [Electrolysis System]

[0329] The above-mentioned unipolar electrolytic cell is assembled in Figure 4 The electrolysis apparatus 70 shown is used for alkaline water electrolysis. Hereinafter, refer to... Figure 4 An overview of the electrolysis system is provided.

[0330] A 30% KOH aqueous solution is sealed in the gas-liquid separator 72 and the external manifold type unipolar electrolyzer 50 as the electrolyte. This electrolyte circulates between the anode chamber and the anode gas-liquid separator (oxygen separator 72o), and between the cathode chamber and the cathode gas-liquid separator (hydrogen separator 72h), respectively, via a pump 71. The electrolyte flow rate is measured by a flow meter 77 and adjusted to 0.3 L / min, and the temperature is adjusted to 80°C by a strip heater 79. SUS316 10AA piping is used at the electrolyte contact point in the circulation path.

[0331] Gas-liquid separators 72 (72h and 72o) are 240mm high and 2.3L in volume. The liquid volume in each of the gas-liquid separators 72h and 72o is approximately 50% of the design volume.

[0332] The rectifier 74 supplies current to the cathodes and anodes of each electrolysis unit at a specified electrode density.

[0333] It should be noted that the rectifier 74 uses the ZX-S-800LAN from Takasago Manufacturing Co., Ltd.

[0334] The hydrogen concentration meter 76 uses the SD-1D manufactured by Riken Keiki Co., Ltd.

[0335] As the pressure gauge 78, the KP15-17G manufactured by Nagano Keiki Co., Ltd. is used.

[0336] The flow meter 77, the strip heater 79, the liquid delivery pump 71, the gas-liquid separator 72 (72h and 72o), the water supply device 73, etc., all use devices commonly used in this technical field.

[0337] (External leakage test)

[0338] After immersing the diaphragm in ethanol for 1 minute, it is then immersed in distilled water for 4 minutes, replacing the inside (pores) of the diaphragm with distilled water. This operation is performed at room temperature. After immersion in distilled water, the diaphragm is quickly assembled into a unipolar electrolyzer. The unipolar electrolyzer is then assembled into the electrolysis apparatus, and a portable pressure gauge (NIDEC COMPONENTS, PG-100-102GP) is connected to conduct an airtightness test inside the unipolar electrolyzer. Pressurized air of approximately 3 kPa is introduced into the electrolyzer, and the pressure is measured immediately after sealing the electrolyzer and after one minute. The results are evaluated according to the following evaluation criteria.

[0339] A (Excellent): Pressure is maintained, and pressure fluctuations are less than 3%.

[0340] B (Poor): The pressure is maintained, but the pressure fluctuation exceeds 3%.

[0341] C (Poor): Pressure was not maintained and decreased rapidly.

[0342] (Initial short-circuit test)

[0343] For diaphragms rated A in the external leakage test, continue supplying electrolyte to the same electrolysis unit until the electrolytic cell is filled with room temperature electrolyte. Use a digital multimeter (Custom, CDM-2000D) to measure the resistance between the anode and cathode, and evaluate according to the following evaluation criteria.

[0344] A (Excellent): The resistance between the anode and cathode is 1 kΩcm. 2 above

[0345] B (Poor): The resistance between the anode and cathode is less than 1 kΩcm. 2

[0346] (Initial Characteristic Measurement)

[0347] For diaphragms that received an A rating in the initial short-circuit test, the same electrolysis apparatus was continued to be used at an electrolyte temperature of 80℃ and a current of 6kA / m. 2 Alkaline water electrolysis was performed by continuously applying current at a certain current density for 1 hour. After 1 hour, the current density was changed to 1 kA / m. 2 This increases the current density by 1 kA / m each time. 2 Up to 15kA / m 2The voltage (V) of the electrolysis unit was measured each time. It should be noted that electrolysis was stopped when the current density reached 2.4V during the increase. The initial characteristics at this point were evaluated according to the evaluation criteria below. Additionally, 15kA / m... 2 The voltage of the electrolytic cell under the given conditions is shown as cell voltage (V) in Table 2.

[0348] A (Excellent): At 15kA / m 2 Under the condition of below 2.35V

[0349] B (Poor): At 5kA / m 2 Above and below 15kA / m 2 Under conditions exceeding 2.35V

[0350] C (difference): less than 5kA / m 2 Under conditions exceeding 2.35V

[0351] (Example 1)

[0352] Twenty parts by weight of PE with a viscosity-average molecular weight of 4 million were fed into the feed inlet of a co-rotating twin-screw extruder via a feeder. Meanwhile, liquid paraffin with a kinematic viscosity of 82 cSt at 38°C, used as a pore-forming material, was added twice via a side feed to the barrel of the twin-screw extruder, with a liquid paraffin content of 80 parts by weight in the total mixture (100 parts by weight) extruded through melt mixing. The ratio of the two additions was 3:1 (first addition / second addition), and the temperature of the liquid paraffin at the time of addition was 120°C. The melt mixing conditions were set to a screw speed of 250 rpm and an extrusion rate of 15 kg / h. The set temperatures were 200°C for both the mixing section and the slit nozzle. Next, the melt mixture exiting the 7 mm slit nozzle was air-cooled on a mesh conveyor to obtain a final compound.

[0353] Next, the above-mentioned compound was pressed at 225°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a blank sheet with a thickness of 3 mm. The blank sheet was then placed in a simultaneous biaxial stretching machine and simultaneously biaxially stretched at 125°C with a relaxation stretch ratio of 4.0 × 4.0, followed by a relaxation operation at a relaxation rate of 5.4%. The stretched blank sheet was then removed and fixed to a stainless steel frame using clamps. In this state, it was immersed in dichloromethane to extract the pore-forming material, dried at room temperature to remove the dichloromethane, and then heat-set in an oven at 133°C for 0.5 hours to obtain a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0354] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0355] (Example 2)

[0356] The stretching temperature was changed to 126°C, and the process was otherwise the same as in Example 1 to obtain a porous membrane and a separator. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and separator are shown in Table 2.

[0357] (Example 3)

[0358] The stretching temperature was changed to 128°C, and the process was otherwise the same as in Example 1 to obtain a porous membrane and a separator. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and separator are shown in Table 2.

[0359] (Example 4)

[0360] The mass fraction of PE during melt mixing was changed to 25 parts by mass, the mass fraction of liquid paraffin was changed to 75 parts by mass, and the stretching temperature was changed to 126°C. All other procedures were performed in the same manner as in Example 1 to obtain a porous membrane and a separator. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and separator are shown in Table 2.

[0361] (Example 5)

[0362] Using PE with a viscosity-average molecular weight of 7.5 million, the mass fraction of PE during melt mixing was 22.2 parts by mass, and the mass fraction of liquid paraffin was 77.8 parts by mass. The addition ratio of liquid paraffin was 1:1 for the first and second applications. The extrusion rate was 10 kg / h, and the set temperatures were 205°C for both the mixing section and the slit nozzle. The stretching conditions were set at a stretching temperature of 120°C, a stretching ratio of 3.5 × 3.5, and a heat setting temperature of 130°C. All other conditions were the same as in Example 1, resulting in a porous membrane and a separator. The manufacturing conditions for the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and separator are shown in Table 2.

[0363] (Example 6)

[0364] PE with a viscosity-average molecular weight of 2 million, tetra[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane as an antioxidant at 0.3% by mass relative to PE, and liquid paraffin with a kinematic viscosity of 82 cSt at 38°C as a pore-forming material were mixed at a PE / pore-forming material ratio of 18 / 82 and kneaded at 200°C using a Labo Plastomill (manufactured by Toyo Seiki Co., Ltd.).

[0365] Next, the above-mentioned compound was pressed at 200°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a 3 mm thick blank. The blank was then cooled at 20°C to produce a 3 mm thick preform. The preform was placed in a biaxial stretching machine and subjected to successive biaxial stretching at 120°C with a relaxation ratio of 5.0 × 5.0, followed by a relaxation operation at a relaxation rate of 5.4%. The stretched preform was then removed and fixed to a stainless steel frame using clamps. In this state, it was immersed in dichloromethane to extract the pore-forming material, and then dried at room temperature to remove the dichloromethane, thus obtaining a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0366] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0367] (Example 7)

[0368] PE with a viscosity-average molecular weight of 900,000, tetra[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane as an antioxidant at 0.3% by mass relative to PE, and liquid paraffin with a kinematic viscosity of 82 cSt at 38°C as a pore-forming material were mixed at a PE / pore-forming material ratio of 30 / 70 and kneaded at 200°C using a Labo Plastomill (manufactured by Toyo Seiki Co., Ltd.).

[0369] Next, the above-mentioned compound was pressed at 200°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a 3 mm thick blank sheet, which was then cooled at 20°C. The blank sheet was placed in a biaxial stretching machine and simultaneously biaxially stretched at 125°C with a relaxation ratio of 4.0 × 4.0, followed by a relaxation operation at a relaxation rate of 5.4%. The stretched blank sheet was then removed and fixed to a stainless steel frame using clamps. In this state, it was immersed in dichloromethane to extract the pore-forming material, dried at room temperature to remove the dichloromethane, and then heat-set in a 130°C oven for 0.5 hours to obtain a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0370] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0371] (Example 8)

[0372] Using PE with a viscosity-average molecular weight of 2 million, the PE / pore-forming material ratio was set to 25 / 75 (mass ratio), the stretching temperature was set to 120°C, the stretching ratio was set to 3.5 × 3.5, and the heat setting temperature was changed to 125°C. All other procedures were performed in the same manner as in Example 7 to obtain porous membranes and separators. The manufacturing conditions of the porous membranes are shown in Table 1, and the evaluation results of the obtained porous membranes and separators are shown in Table 2.

[0373] (Example 9)

[0374] The PE / pore-forming material ratio was set to 25 / 75 (by mass), the stretching temperature was set to 120°C, the stretching ratio was set to 6.0 × 6.0, and the heat setting temperature was changed to 125°C. All other procedures were performed in the same manner as in Example 1 to obtain a porous membrane and a separator. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and separator are shown in Table 2.

[0375] (Example 10)

[0376] PE with a viscosity-average molecular weight of 2 million and high molecular weight PE with a viscosity-average molecular weight of 300,000 were mixed at a mass ratio of 1:1 (the contact angle of the mixture with water was 94°). Tetra-[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, which is used as an antioxidant, at a mass ratio of 0.3% relative to the total PE, and liquid paraffin with a kinematic viscosity of 82 cSt at 38°C, which is used as a pore-forming material, were mixed at a mass ratio of PE total / pore-forming material = 25 / 75. The mixture was then kneaded at 200°C using a Labo Plastomill (manufactured by Toyo Seiki Co., Ltd.).

[0377] Next, the above-mentioned compound was pressed at 200°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a 3 mm thick blank sheet, which was then cooled at 20°C. The blank sheet was placed in a biaxial stretching machine and simultaneously biaxially stretched at 125°C with a relaxation ratio of 4.0 × 4.0, followed by a relaxation operation at a relaxation rate of 5.4%. The stretched blank sheet was then removed and fixed to a stainless steel frame using clamps. In this state, it was immersed in dichloromethane to extract the pore-forming material, dried at room temperature to remove the dichloromethane, and then heat-set in a 130°C oven for 0.5 hours to obtain a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0378] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0379] (Example 11)

[0380] 25 parts by weight of PE with a viscosity-average molecular weight of 2 million were fed into the feed inlet of a co-rotating twin-screw extruder via a feeder. Meanwhile, liquid paraffin with a kinematic viscosity of 82 cSt at 38°C, used as a pore-forming material, was added twice via a side feed to the barrel of the twin-screw extruder, with a liquid paraffin content of 75 parts by weight in the total mixture (100 parts by weight) extruded through melt mixing. The ratio of the two additions was 4:1 (first addition / second addition), and the temperature of the liquid paraffin at the time of addition was 120°C. The melt mixing conditions were set to a screw speed of 250 rpm and an extrusion rate of 20 kg / h. The set temperatures were 200°C for both the mixing section and the slit nozzle. Next, the melt mixture exiting the 7 mm slit nozzle was air-cooled on a mesh conveyor to obtain a final compound.

[0381] Next, the above-mentioned compound was pressed at 225°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a 3 mm thick blank. The blank was then cooled at 20°C to produce a 3 mm thick sheet. The blank was fixed to a stainless steel frame using clamps, and in this state, it was immersed in dichloromethane to extract the pore-forming material. The dichloromethane was then removed by drying at room temperature. The blank was then placed in a biaxial stretching machine and simultaneously biaxially stretched at 125°C with a relaxation stretch ratio of 4.0 × 4.0. After relaxation at a rate of 5.4%, the sheet was heat-set in a 130°C oven for 0.5 hours to obtain a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0382] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0383] (Example 12)

[0384] High molecular weight PE with a viscosity-average molecular weight of 300,000, tetra[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane (at 0.3% by mass relative to the high molecular weight PE as an antioxidant), and liquid paraffin with a kinematic viscosity of 82 cSt at 38°C as a pore-forming material were mixed at a PE / pore-forming material ratio of 25 / 75 and kneaded at 200°C using a LaboPlastomill (manufactured by Toyo Seiki Co., Ltd.).

[0385] Next, the above-mentioned compound was pressed at 200°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a 3 mm thick blank. The blank was then cooled at 20°C to produce a blank sheet. The blank sheet was fixed to a stainless steel frame with clamps, and in this state, it was immersed in dichloromethane to extract the pore-forming material. The dichloromethane was then removed by drying at room temperature. The blank sheet was then placed in a biaxial stretching machine and simultaneously biaxially stretched at 125°C with a relaxation stretch ratio of 2.5 × 2.5. After relaxation at a rate of 5.4%, it was heat-set in an oven at 130°C for 0.5 hours to obtain a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0386] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0387] (Example 13)

[0388] 25 parts by mass of PE with a viscosity-average molecular weight of 2 million, 1 part by mass of tetramethyl-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate as an antioxidant, 50 parts by mass of dioctyl phthalate as a pore-forming material, and 25 parts by mass of micronized silica (Nipsil LP manufactured by Tosoh Silica) were mixed and kneaded at 200°C using a Labo Plastomill (manufactured by Toyo Seiki Co., Ltd.).

[0389] Next, the compound was pressed at 200°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a blank sheet, which was then cooled at 20°C to produce a 2.5 mm thick blank sheet. The blank sheet was then fixed to a stainless steel frame using clamps. In this state, it was immersed in dichloromethane to extract the pore-forming material, then immersed in ethanol, and finally immersed in a 30% potassium hydroxide aqueous solution heated to 90°C to extract and remove the micronized silica from the blank sheet. The sheet was then washed to remove the alkali and dried in an oven to remove moisture, yielding a blank sheet for stretching.

[0390] The preform for stretching was placed in a biaxial stretching machine and simultaneously biaxially stretched at 125°C with a relaxation stretch ratio of 6.0 × 4.0. After relaxation, a relaxation rate of 3.2% was applied, followed by heat setting in a 130°C oven for 0.5 hours to obtain a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0391] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0392] (Example 14)

[0393] Using high molecular weight PE with a viscosity-average molecular weight of 300,000, the stretch ratio was changed to 2.5 × 2.5 times, and the porous membrane and diaphragm were fabricated in the same manner as in Example 13. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and diaphragm are shown in Table 2.

[0394] (Example 15)

[0395] Using high molecular weight PE with a viscosity-average molecular weight of 700,000, the stretching temperature was changed to 130°C, and the porous membrane and separator were fabricated in the same manner as in Example 13. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and separator are shown in Table 2.

[0396] (Example 16)

[0397] Twenty parts by mass of zirconium oxide (SPZ, manufactured by Daiichi Rare Element Chemical Industry Co., Ltd.), an inorganic compound with an average primary particle size of 300 nm, and twenty parts by mass of polyethylene with a viscosity-average molecular weight of 4 million were fed into a separate feed port of a co-rotating twin-screw extruder via separate feeders. Additionally, liquid paraffin, a pore-forming material with a kinematic viscosity of 82 cSt at 38°C, was added twice via side feed to the barrel of the twin-screw extruder, with a liquid paraffin content of 60 parts by mass in the total mixture (100 parts by mass) extruded through melt mixing. The ratio of the two additions was 2:1 (first addition / second addition), and the temperature of the liquid paraffin at the time of addition was 115°C. The melt mixing conditions were set to a screw speed of 250 rpm and an extrusion rate of 10 kg / h. The set temperatures were 210°C for the mixing section and 205°C for the slit nozzle. The melt mixture exiting the 7 mm slit nozzle was then air-cooled on a mesh conveyor to obtain a compound.

[0398] Next, the above-mentioned compound was pressed at 225°C and 15 MPa using a small testing press (manufactured by Toyo Seiki Co., Ltd.) to form a blank sheet with a thickness of 3 mm. The blank sheet was then placed in a simultaneous biaxial stretching machine and simultaneously biaxially stretched at 120°C with a relaxation ratio of 3.5 × 3.5, followed by a relaxation operation at a relaxation rate of 5.4%. The stretched blank sheet was then removed and fixed to a stainless steel frame using clamps. In this state, it was immersed in dichloromethane to extract the pore-forming material, dried at room temperature to remove the dichloromethane, and then heat-set in a 125°C oven for 0.5 hours to obtain a porous membrane. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane are shown in Table 2.

[0399] The porous membrane was immersed in ethanol for 1 minute, then in distilled water for 4 minutes to prepare a membrane with the pores filled with distilled water, which was then used as a diaphragm. The evaluation results of the diaphragm are shown in Table 2.

[0400] (Comparative Example 1)

[0401] The porous membrane and diaphragm were prepared in the same manner as in Example 5, with PE comprising 25 parts by mass and liquid paraffin comprising 75 parts by mass during melt mixing, without heat setting. The manufacturing conditions of the porous membrane are shown in Table 1, and the evaluation results of the obtained porous membrane and diaphragm are shown in Table 2.

[0402] Initial characteristics were measured, and results were obtained at a current density of 13 kA / m. 2 Under conditions exceeding 2.35V, at 14kA / m 2 The voltage reaches 2.4V under certain conditions, therefore electrolysis is stopped. In other words, this diaphragm cannot simultaneously achieve both airtightness and low cell voltage.

[0403] (Comparative Example 2)

[0404] The proportions of PE and liquid paraffin during melt mixing were 27.3 parts by mass and 72.7 parts by mass, respectively. The stretching temperature was changed to 128°C and the heat setting temperature was changed to 136°C. Otherwise, the process was the same as in Example 1 to produce porous membranes and diaphragms. The manufacturing conditions of the porous membranes are shown in Table 1, and the evaluation results of the obtained porous membranes and diaphragms are shown in Table 2.

[0405] Initial characteristics were measured, and results were obtained at a current density of 2 kA / m. 2 Under certain conditions, the voltage exceeds 2.35V, reaching 2.4V, thus stopping electrolysis. In other words, the diaphragm cannot simultaneously achieve both airtightness and low cell voltage.

[0406] [Table 1]

[0407] [Table 2]

[0408] Industrial applicability

[0409] The alkaline water electrolysis diaphragm according to the present invention has good airtightness even when using sheet gaskets, can perform water electrolysis at low cell voltage, and is suitable for the production of hydrogen by water electrolysis.

[0410] Explanation of reference numerals in the attached figures

[0411] 1. Next door

[0412] 2a Anode

[0413] 2c cathode

[0414] 2e Conductive elastomer

[0415] 2r collector

[0416] 3. Outer frame

[0417] 4. Diaphragm

[0418] 5 Electrode Chambers

[0419] 5a Anode Chamber

[0420] 5c Cathode Chamber

[0421] 50 electrolytic cells

[0422] 51a Anode Terminal Component

[0423] 51c Cathode Terminal Element

[0424] 51g Fastening head, movable head

[0425] 51i Insulation Board

[0426] 51r pull rod

[0427] 6 Rectifier Board

[0428] 60 components

[0429] 65 Electrolysis Units

[0430] 7. Gasket section

[0431] 70 Alkaline water electrolysis device

[0432] 71 Liquid delivery pump

[0433] 72h Cathode-side Gas-Liquid Separator (Hydrogen Separator)

[0434] 72° Anode-side gas-liquid separator (oxygen separator)

[0435] 73 Water supply unit

[0436] 74 Rectifier

[0437] 75 Oxygen Concentration Meter

[0438] 76 Hydrogen Concentration Meter

[0439] 77 Flow Meter

[0440] 78 Pressure gauge

[0441] 79 Heat Exchanger

[0442] 80 Pressure control valve

[0443] Z zero-gap structure

[0444] D1 Predetermined direction

Claims

1. A method of use, characterized in that, A porous membrane containing polyethylene, with a polyethylene content of 50% or more in the resin component and a tortuosity of 3.00 or less, is used as a diaphragm for alkaline water electrolysis.

2. The method of use according to claim 1, wherein, The thickness of the porous membrane is between 40 μm and 1000 μm.

3. The method of use according to claim 1 or 2, wherein, The tortuosity of the porous membrane is between 0.30 and 2.

50.

4. The method of use according to claim 1 or 2, wherein, The tortuosity of the porous membrane is above 1.00 and below 2.

50.

5. The method of use according to claim 1 or 2, wherein, The porosity of the porous membrane is above 20% and below 95%.

6. The method of use according to claim 1 or 2, wherein, The water permeability of the porous membrane is between 0.1g / 2 minutes and 500g / 2 minutes.

7. The method of use according to claim 1 or 2, wherein, The air permeability of the porous membrane, converted to 100μm, is between 10 seconds and 4000 seconds.

8. The method of use according to claim 1 or 2, wherein, The viscosity-average molecular weight of the polyethylene is between 300,000 and 7.5 million.

9. A diaphragm for alkaline water electrolysis, characterized in that, It comprises a porous membrane containing polyethylene, wherein the polyethylene content in the resin component of the porous membrane is 50% by mass or more, and the tortuosity of the porous membrane is 3.00 or less.

10. The diaphragm for alkaline water electrolysis according to claim 9, wherein, The film thickness is between 40 μm and 1000 μm.

11. The diaphragm for alkaline water electrolysis according to claim 9 or 10, wherein, The tortuosity of the porous membrane is between 0.30 and 2.

50.

12. The diaphragm for alkaline water electrolysis according to claim 9 or 10, wherein, The tortuosity of the porous membrane is above 1.00 and below 2.

50.

13. The diaphragm for alkaline water electrolysis according to claim 9 or 10, wherein, The porosity of the porous membrane is above 20% and below 95%.

14. The diaphragm for alkaline water electrolysis according to claim 9 or 10, wherein, The water permeability of the porous membrane is between 0.1g / 2 minutes and 500g / 2 minutes.

15. The diaphragm for alkaline water electrolysis according to claim 9 or 10, wherein, The air permeability of the porous membrane, converted to 100μm, is between 10 seconds and 4000 seconds.

16. The diaphragm for alkaline water electrolysis according to claim 9 or 10, wherein, The viscosity-average molecular weight of the polyethylene is between 300,000 and 7.5 million.

17. An electrolytic cell for alkaline water electrolysis, comprising: The diaphragm for alkaline water electrolysis as described in claim 9 or 10; Anode; and cathode, The diaphragm for alkaline water electrolysis is disposed between the anode and the cathode.

18. An electrolytic cell for alkaline water electrolysis, comprising: The diaphragm for alkaline water electrolysis as described in claim 9 or 10; Sheet gaskets; Anode; and cathode, The diaphragm for alkaline water electrolysis is disposed between the anode and the cathode.

19. An electrolytic cell for alkaline water electrolysis, comprising: The diaphragm for alkaline water electrolysis as described in claim 9 or 10; Two sheet-like gaskets; Anode; and cathode, The diaphragm for alkaline water electrolysis is disposed between the anode and the cathode, and the two sheet-like gaskets are arranged to clamp the diaphragm for alkaline water electrolysis.

Citation Information

Patent Citations

  • Diaphragm for alkaline electrolysis cells and batteries

    FR2546535A1

  • Preparation of a membrane and its use in an electrochemical cell

    WO1993015529A1

  • Electrolytic membrane

    WO2014119207A1

  • Electrolytic membrane

    WO2014119208A1

  • Diaphragm, electrolytic bath, and method for producing hydrogen

    WO2018182006A1